Method for purification of bisphenol a dianhydride composition, method for preparing poly(etherimide) derived from bisphenol a dianhydride composition, and method for forming articles from poly(etherimide)
Patent Information
- Application Number
- JP2024207265
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-01-31
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 2025032170000018 
Figure 2025032170000019 
Figure 2025032170000020
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for the purification of a bisphenol A dianhydride composition, Dianhydride compositions, poly(etherimides) derived from bisphenol A dianhydride compositions ), and articles prepared therefrom.
[0002] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of European Patent Application No. 19154904.7, filed January 31, 2019. No. 6,399,433, the contents of which are incorporated herein by reference in their entirety. [Background technology]
[0003] Poly(imides), especially poly(etherimide) (PEI), have a much higher thermal stability at 180°C. These polymers are high performance polymers having a glass transition temperature (Tg) of 0.1 to 1.0 μm. , high strength, heat resistance, and modulus, as well as broad chemical resistance. Poly(ether Imides) are widely used in applications as diverse as automotive and electrical / electronic applications. Why? These compositions are preferred because they offer good mechanical and thermal properties.
[0004] Poly(ether imides) are prepared, for example, by the condensation polymerization of dianhydrides with diamines. To obtain good reaction kinetics, to achieve high molecular weight, and to obtain stable To provide a processable polymer product, a high purity monomer component is desirable. In addition, some applications require polymers that offer good optical clarity as well as good thermal and The level of haze exhibited by the manufactured product may be determined by the In practice, the alkali metals and their salts are essentially It can be difficult to produce the desired dianhydride that is free from Summary of the Invention [Problem to be solved by the invention]
[0005] Thus, in the art, residual phase transfer agents such as sodium, potassium, calcium, and zinc are Lead, aluminum, iron, titanium, phosphorus, phosphate, nitrate, nitrite, sulfate, and chloride ions There is a need for dianhydride monomers that are substantially free of amines. It has low haze, high optical clarity, good reaction kinetics during polymerization, and high Poly(etherimides) that exhibit molecular weight and behave as stable and processable polymers It would be a further advantage to provide [Means for solving the problem]
[0006] A method for purifying a bisphenol A dianhydride composition comprising: contacting the product composition with a halogenated solvent to form a solution; and filtering the solution to remove ionic species. the solution is washed with an aqueous medium to remove ionic species; The ionic species were removed by crystallizing aryl dianhydride from solution and by using the solution as an adsorbent. and removing ionic species; The bisphenol A dianhydride composition has the formula [ka] Bisphenol A dianhydride [wherein R a and R b are each independently halogen or is monovalent C 1-6is an alkyl group, and p and q are each independently an integer from 0 to 4; Preferably, p and q are each 0; and sodium, potassium, calcium, Sium, zinc, aluminum, iron, titanium, phosphorus, phosphate, nitrate, nitrite, sulfate, and and at least one chloride ion.
[0007] Purified bisphenol A dianhydride contains less than 25 ppm of sodium ion, calcium ion, and potassium ion. Lithium ion, calcium ion, zinc ion, aluminum ion, iron ion, titanium ions, and phosphorus ions, as well as less than 50 ppm each of phosphate ions, sulfate ions, salt ions These include chloride ions, nitrate ions, and nitrite ions.
[0008] The polymerisation of purified bisphenol A dianhydride composition with organic diamines results in a repeating product. A poly(etherimide) containing repeating units.
[0009] Articles of manufacture comprising poly(etherimides) represent another aspect of the present disclosure.
[0010] The above described and other features are illustrated by the following figures and detailed description.
[0011] The following figures correspond to exemplary embodiments. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 shows the reduction in the amount of sodium ions versus the total volume of water used for washing. [Diagram 2] FIG. 1 shows the effect of NaHCO3 concentration on the ring opening of bisphenol A dianhydride. [Diagram 3] FIG. 1 shows the effect of Na2CO3 concentration on the ring opening of bisphenol A dianhydride. [Figure 4]FIG. 2 shows the effect of NaOH concentration on the ring opening of bisphenol A dianhydride. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present inventors have developed an improvement for the purification of bisphenol A dianhydride using halogenated solvents. Advantageously, highly pure bisphenol A dianhydride is reacted with an organic acid , organic acid anhydrides, or both, e.g., acetic acid or acetic anhydride, without the use of acetic acid. Bisphenol A dianhydride can be used as a contaminant, such as a phase transfer agent, and Sodium, potassium, calcium, zinc, aluminum, titanium, iron, phosphorus, phosphate It is substantially free of various inorganic ion species, including nitrate, nitrite, sulfate, and chloride ions. Bisphenol A dianhydride has high thermal performance, low water absorption, and good mechanical properties. Poly(ether)s having desirable properties including high solubility and improved flow at high shear. This is particularly useful for the preparation of aryl imides.
[0014] Accordingly, certain aspects of the present disclosure relate to a method for purifying a bisphenol A dianhydride composition. In one embodiment, the method disclosed herein comprises the steps of: 60 percent by weight or more of bisphenol A dianhydride, based on the total weight of the dianhydride composition Water or 70 weight percent or more of bisphenol A dianhydride or 80 weight percent 90 weight percent or more of bisphenol A dianhydride or 90 weight percent or more of bisphenol A method for the purification of a bisphenol A dianhydride composition comprising bisphenol A dianhydride. The phenol A dianhydride composition has the formula [ka] wherein R a and R b are each independently haloge CN or monovalent C 1-6 is an alkyl group, and p and q are each independently an integer from 0 to 4. Preferably, p and q are each 0. In some embodiments, p, q, or both can be 1 to 4, preferably 1 to 2, and more preferably 1. In some embodiments, R a and R b are each independently C 1-3 Alkyl groups, e.g. The divalent bond of the biphenol group can be in the 3,3' position, the 3,4' position, or the 4, Preferably, the divalent bond of the biphenol group is at the 3,3' position. In some embodiments, the bisphenol A dianhydride may be an isomeric mixture. For example, 10 to 100 percent by weight of bisphenol A dianhydride may be bisphenol A. The divalent bond of the bisphenol A group of phenol A dianhydride is at the 3,3' position. Bisphenol A dianhydride is 90 to 100 weight percent bisphenol dianhydride. The compound has divalent bonds of bisphenol A groups at the 3,3' positions.
[0015] In addition to bisphenol A dianhydride, the bisphenol A dianhydride composition may also include sodium Calcium ion, potassium ion, calcium ion, zinc ion, aluminum ion, Sodium ion, iron ion, phosphorus ion, phosphate ion, sulfate ion, phosphate ion, chloride ions, nitrate ions, and nitrite ions. The formula (I) is a carboxylic acid dianhydride composition containing more than 1000 ppm of each of the aforementioned ionic species, or more than 5000 ppm of each of the aforementioned ionic species. In some embodiments, the bisphenol A may contain more than 10,000 ppm of bisphenol A. The aryl A dianhydride composition is equal to or greater than 25 ppm, or greater than 100 ppm, or or more than 200 ppm sodium ions.
[0016] In some embodiments, the bisphenol A dianhydride composition comprises a bisphenol A dianhydride. hydrolysis of the imide to form the corresponding tetrasalt of bisphenol A tetraacid; Quenching the tetrasalt of phenol A tetraacid with mineral acids to form bisphenol A tetraacid. contacting bisphenol A tetraacid with a halogenated solvent to form a reaction mixture; The reaction mixture is heated to an effective temperature to convert the corresponding bisphenol A dianhydride into bisphenol A dianhydride. from bisphenol A tetraacid, optionally in the presence of a mineral acid, and and isolating the hydrate from the reaction mixture. The method of making the A dianhydride composition preferably comprises the step of: It is carried out in the presence of
[0017] The method for the purification of a bisphenol A dianhydride composition comprises: In some embodiments, the halogenated solvent is contacted with the product composition to form a solution. In the present study, the halogenated solvent is an aromatic halogenated solvent, such as ortho-dichlorobenzene, Dichlorobenzene, meta-dichlorobenzene, trichlorobenzene, or any of their It's a combination.
[0018] The method further comprises filtering the solution to remove ionic species, washing the solution with an aqueous medium, and bisphenol A dianhydride was crystallized from solution to remove the ionic species. and contacting the solution with a sorbent to remove ionic species. In some embodiments, the method includes one of the above. In some embodiments, The method includes at least two of the aforementioned steps for removing ionic species. In an embodiment, the method includes at least three of the aforementioned steps for removing ionic species. In some embodiments, the method further comprises the steps of: Includes.
[0019] In certain embodiments, the method includes filtering the solution to remove ionic species. It is preferable to form the solution into a particle size of less than or equal to 2 micrometers. Preferably less than 1 micrometer, more preferably between 0.2 and 0.45 micrometers. This may include passing the sample through a filter having a pore size.
[0020] In some embodiments, the method includes washing the solution with an aqueous medium. may contain an aqueous caustic solution. The aqueous caustic solution may be, for example, an aqueous solution of an alkali metal bicarbonate, such as sodium bicarbonate. Preferably, the aqueous alkali metal bicarbonate solution is It may have a concentration of 1 to 10 weight percent based on the total weight.
[0021] In one embodiment, the method includes crystallizing bisphenol A dianhydride from solution. The crystallization of bisphenol A dianhydride may optionally include adding a poor solvent to the solution. and cooling the solution to an effective temperature to provide a slurry. In some embodiments, the anti-solvent is heptane, hexane, pentane , benzene, ligroin, or combinations thereof. The anti-solvent can include heptane. Cooling the solution can be, for example, from 20 to 100° C. The temperature may be from 50 to 100°C, or from 65 to 85°C.
[0022] In some embodiments, the method includes contacting the solution with an adsorbent. The adsorbent may be, for example, a ceramic. The method may further comprise the step of: Then, the solution containing the adsorbent is subjected to a sieve of 60 micrometers or less, preferably 40 to 60 micrometers. The method may include filtering the mixture through a filter having a pore size of 100 ml.
[0023] The methods of the present disclosure can provide purified bisphenol A dianhydride. Phenol A dianhydride contains less than 25 ppm each of sodium ion, potassium ion, and calcium ion. Calcium ion, zinc ion, aluminum ion, titanium ion, iron ion, and lithium ion. For example, purified bisphenol A dianhydride may contain 1 to 25 cations each. Sodium ions, potassium ions, calcium ions, zinc ions, and aluminum ions less than ppm The purified bicarbonate may contain ions such as aluminum ions, titanium ions, iron ions, and phosphorus ions. Sphenol A dianhydride contains less than 50 ppm each of phosphate ion, sulfate ion, and chloride ion. For example, purified bisphenol A Acid dianhydrides contain 1 to 50 ppm each of phosphate ion, sulfate ion, chloride ion, and nitrate ion. It may contain acid ions, and nitrite ions.
[0024] Bisphenol A dianhydride made by the method of the present disclosure represents another embodiment of the present disclosure. Bisphenol A dianhydride: Less than 25 ppm or 1 to 25 ppm each Sodium ion, potassium ion, calcium ion, zinc ion, aluminum ion Nitrogen, titanium ions, iron ions, and phosphorus ions, and each less than 50 ppm or less than 1 Less than 50 ppm of phosphate, sulfate, chloride, nitrate, and nitrite Contains acid ions.
[0025] The bisphenol A dianhydrides of the present disclosure are particularly useful for the preparation of poly(etherimides). Therefore, the purified bisphenol A dianhydride composition and the organic diamine can be used. It is a poly(etherimide) containing repeat units derived from the polymerization of bisphenol A. The dianhydride may be purified according to the methods described herein, and thus advantageously contains low levels of may have contaminants.
[0026] The organic diamines are 1,4-butanediamine, 1,5-pentanediamine, and 1,6-hexanediamine. Sandiamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonane Diamine, 1,10-decanediamine, 1,12-dodecanediamine, 1,18-octa Decanediamine, 3-methylheptamethylenediamine, 4,4-dimethylheptamethylene Diamine, 4-methylnonamethylenediamine, 5-methylnonamethylenediamine, 2,5 -Dimethylhexamethylenediamine, 2,5-dimethylheptamethylenediamine, 2,2 -Dimethylpropylenediamine, N-methyl-bis(3-aminopropyl)amine, 3- Methoxyhexamethylenediamine, 1,2-bis(3-aminopropoxy)ethane, Bis (3-aminopropyl) sulfide, 1,4-cyclohexanediamine, bis-(4-aminopropyl) (aminocyclohexyl)methane, m-phenylenediamine, p-phenylenediamine, 2, 4-Diaminotoluene, 2,6-diaminotoluene, m-xylylenediamine, p-xylylenediamine Rylenediamine, 2-methyl-4,6-diethyl-1,3-phenylenediamine, 5- Methyl-4,6-diethyl-1,3-phenylene-diamine, benzidine, 3,3'-di Methylbenzidine, 3,3'-dimethoxybenzidine, 1,5-diaminonaphthalene, biphenyls Bis(4-aminophenyl)methane, Bis(2-chloro-4-amino-3,5-diethyl phenyl)methane, bis(4-aminophenyl)propane, 2,4-bis(p-amino-t -butyl)toluene, bis(p-amino-t-butylphenyl)ether, bis(p-methyl Bis(p-methyl-o-aminopentyl)benzene 1,3-diamino-4-isopropylbenzene, bis(4-aminophenyl)sulfur , bis-(4-aminophenyl)sulfone (4,4'-diaminodiphenylsulfone (also known as DDS), and bis(4-aminophenyl) ether. Any positional isomer of the aforementioned compounds may be used. 1-4 a Alkylation or poly(C 1-4 ) alkylated derivatives, e.g. polymethylated 1,6-hexa Combinations of these compounds may also be used. In one embodiment, the organic diamine is 4,4'-diaminodiphenylsulfone, 3,4'-diaminodiphenylsulfone, Aminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, meta-phenylene diamine, para-phenylenediamine, ortho-phenylenediamine, or a combination thereof It is a combination.
[0027] Purified bisphenol A dianhydride and organic diamines can be conjugated under effective conditions. The purified bisphenol A acid is contacted with the poly(etherimide) to provide a poly(etherimide). The aqueous solution and the organic diamine are contacted in the presence of a solvent, for example a halogenated solvent. In a specific embodiment, the halogenated solvent can include ortho-dichlorobenzene. Effective conditions for providing poly(etherimide)s include a temperature of 170 to 380° C. and and 1 to 50 weight percent, preferably 20 to 40 weight percent, more preferably The polymerization may include a solids content of 25 to 35 weight percent. The polymerization may be carried out preferably for 3 to 16 hours. The polymerization may be carried out at reduced pressure, atmospheric pressure, or elevated pressure. It can be implemented.
[0028] The method may also optionally employ various chain terminating or endcapping agents, which Thus, the poly(etherimide) may optionally further comprise at least one chain terminator. Chain terminators limit the rate of molecular weight growth and therefore the poly(ether) Exemplary chain terminators include those that can be used to control the molecular weight of the copolymer (imide). Some monoamines (e.g. aniline), monoanhydrides (e.g. phthalic anhydride), and monophenols In some embodiments, the chain terminator is preferably A monoamine chain terminator or a monoanhydride chain terminator, more preferably aniline or anhydride However, any desired weight ratio with any end capping may be used. The poly(etherimide) disclosed herein is produced having a weight average molecular weight (Mw) of It should be understood that this is possible.
[0029] In some embodiments, no catalyst is used in the polymerization of the poly(etherimide).
[0030] The method for making the poly(etherimide) may optionally further include a devolatilization step. Low levels of residual volatile species in the polymer product can be achieved by devolatilization, which is It may also be used to finish off end groups on an article. Most of the solvent may be removed and any remaining volatile species may be removed from the polymer product by devolatilization. Optionally, the polymerization reaction may be carried out in a solvent. The polymerization is then allowed to proceed to some desired level of completion, and the polymerization is then continued until the initial reaction in solution is complete. During at least one devolatilization step following the tial reaction, essentially The polymer mixture is devolatilized and dissolved, which is necessary for good melt processability. Equipment for reducing solvents and other volatile species to low levels is generally capable of high temperature vacuum heating. The mixing of such devices has the ability to rapidly generate a high surface area to aid in the removal of volatile species. The part is generally designed to provide sufficient power to the pump and to pump hot ammonia, which can be very viscous. The rufus poly(etherimide) melt can be agitated and stirred. Suitable devolatilizers include wiped thin film distillation apparatus and devolatilizer extruders, particularly those having multiple vents. In some embodiments, the method includes, but is not limited to, a twin screw extruder having a The process optionally further comprises preheating the poly(etherimide) at 360 to 390°C for 1 to 30 minutes. The method may include devolatilizing the mixture over a period of time.
[0031] Bisphenol A acid purified according to the methods described herein and according to the present disclosure Poly(etherimides) prepared with dianhydrides advantageously have low levels of residual impurities. For example, poly(etherimide) may contain less than 25 ppm each of sodium iodopropionate. ion, potassium ion, calcium ion, zinc ion, aluminum ion, titanium ion ions, iron ions, and phosphorus ions, as well as less than 25 ppm each of phosphate ions, sulfate ions, and ions, chloride ions, nitrate ions, and nitrite ions.
[0032] The poly(etherimides) prepared according to the methods of the present disclosure can be formed into a variety of articles of manufacture. Poly(etherimides) can be particularly useful for polymerizing poly(etherimides) by suitable techniques, e.g., melt They can be formed into articles of manufacture using processing techniques. Melt forming methods include injection molding, extrusion, blow molding, and These methods include molding, rotational molding, coining, and injection blow molding. The process can be injection molding. Poly(etherimide) can be cast, blown, or extruded. These can be further formed into articles of manufacture and structures. These may be thermoformed from the melt or at a later stage in the processing of the composition. Poly(etherimide) can be oriented from different materials or from different processes. The article of manufacture may be overmolded onto an article made by a compression molding or The article may also be formed using techniques such as ram extrusion. Exemplary articles of manufacture include fibers, films, sheets, foams, The polyimide of the present disclosure may be in the form of a filament, a molded product, an extruded product, or a powder. (Etherimides) may also be particularly suitable for use in optoelectronic applications. In particular, poly(ether imides) are used in optoelectronic manufacturing, e.g. They can be used in components such as sensors, receivers, connectors, lenses, waveguides, and the like.
[0033] Thus, purification of bisphenol A dianhydride with low levels of residual contaminants Improved methods for the production of bisphenol A acid diols are provided herein. The anhydrides can be used to prepare poly(etherimides) having desirable properties. These may be particularly useful for a variety of applications, for example in optical manufacturing. EXAMPLES
[0034] The present disclosure is further illustrated by the following non-limiting examples.
[0035] The materials used in the following examples are listed in Table 1.
[0036] [Table 1]
[0037] [Table 2]
[0038] Polymer molecular weights were determined by gel permeation chromatography (GPC) relative to polystyrene standards. It was decided against.
[0039] All ultra-performance liquid chromatography (UPLC) analyses in the following examples were performed using Waters AC QUITY-UPLC-BEH-C18-1.7 micrometer-2.1 x 50 mm The flow was performed at 35°C using a 300-μL column. PDA detection was at 254 nm and 0.313 mL / min. The flow rate was 100 mL / min. Acetonitrile and acidified water (4 L of DI-H2O + 3 mL of 85% H2O) were used. A gradient method using a binary solvent system of 3PO4) was used. In addition, UPLC analysis of BPA-DA revealed a small amount of BPA dianhydride (BPA-AnhDA It is pointed out that this indicates
[0040] The following metals (sodium, potassium, zinc, calcium, aluminum, iron, titanium) All residual levels of cadmium, arsenic, and phosphorus were determined by inductively coupled plasma-decomposition (ICP-Dig) technique. This is done using an ICP spectrometer with axial and / or radial observations. meter, Gem-Cone and / or ultrasonic nebulizer, and appropriate equipment A microwave digestion system is provided with a sample digestion vessel. The sample is It is prepared using concentrated nitric acid, hydrochloric acid, sulfuric acid, and / or hydrofluoric acid.
[0041] Anions present in the BPA-DA and poly(etherimide) samples (sulfate, salt) Residual levels of nitrates, phosphates, nitrates, and nitrites were measured using extraction ion chromatography (IC-IEC). The BPA-DA sample was dissolved in methylene chloride and poly(ether) imide) samples were dissolved in hexafluoroisopropanol (HFIP) to aid in solubility. ) was added to methylene chloride. The solution was then extracted with deionized water. The aqueous extracts were then analyzed using a calibrated Dionex-ICS2000 instrument. .
[0042] Anions present in the BPA-TA sample (sulfate, chloride, phosphate, nitrate, nitrite) The residual levels of were determined by combustion total ion chromatography (IC-total). Measurements were made using a calibrated Dionex-ICS2000 instrument.
[0043] DSC measurements of polymer samples (~5mg) were performed using a TA-Q1000-DSC instrument. The film samples were scanned at temperatures between 40 and 350°C under a nitrogen atmosphere. The glass transition temperature (Tg) and melting point (Tm) of were determined from the second heating scan. A heating rate of 1000 nm was used in these experiments.
[0044] <Examples 1 to 4> Examples 1-4 show various washes to remove sodium from 3,3'-BPA-TA. The efficiency of the method is investigated. Table 2 shows the starting composition of 3,3'-BPA-TA, washing conditions, and In each example, the washings were performed to remove sodium and sulfate from the filtrate. Thorium levels were monitored until they were below 40 ppm. ,3'-BPA-TA was washed at 25°C without agitation using sodium This indicates that 2000 mL of water was required to reduce the amount of malaria to the target level. A similar wash with vigorous agitation at 25°C required only 700 mL of water. Also at 0°C, the amount of water required is approximately the same for the non-agitation wash and The agitated washes were reduced to 900 mL and 500 mL. Shown in 1.
[0045] <Example 5> A mixture of BPA-TA isomers was prepared as described below in Example 14. The TA wet cake was isolated by centrifugation and the filtrate was found to have less than 100 ppm sodium present. The cake was washed several times with DI water until it was found to contain the remaining solids. It had the following profile: ICP-Dig: Sodium (25 ppm), Potassium (6 ppm), zinc (0ppm), calcium (5ppm), aluminum (0ppm), iron (0ppm), Titanium (0ppm), Phosphorus (10ppm), IC-Total: Sulfuric acid (57 ppm), chloride (1,242 ppm), phosphate (<20 ppm), nitrate (304 ppm) ), nitrite (58 ppm), UPLC: 3,3'-BPA-TA (89.8 mol%), 3,4'-BPA-TA (6.75 mol%).
[0046] Prior to the ring closure reaction, both the vessel and the Mott filter were rinsed and washed with DI water. The vessel was then filled with o-DCB (450 kg ), then 150 kg of BPA-TA wet cake containing water (127.9 kg dry weight basis) Nitrogen was added and the mixture (3,3'-BPA-DA) was The mixture was stirred in hot oil (19.9 wt% solids) and then cooled to room temperature. The ed oil was heated to 200-205°C to eliminate water and close the ring. Allow the vessel to concentrate to a total mass of 561 kg (21 wt% solids), if necessary. This level was maintained by adding fresh o-DCB. After 14 hours, over Head analysis showed <30 ppm water present by Karl Fischer analysis. At the same time, the second vessel was thoroughly cleaned with o-DCB for future use. The pan solids analysis of the dianhydride solution showed 19.9 wt% solids. PLC analysis indicated that the reaction was complete. As a result, the solution was heated to 160°C. The mixture was cooled to an internal temperature of 100° C. prior to filtration.
[0047] The Mott filter was heated to 160° C. and the contents of the reactor were then diluted with 2 μl The mixture is then passed through a Lumot filter into a second vessel to remove any residual inorganic species present. A sample of the filtered material was filtered to determine it was 19.7 wt% solids. The filtrate was then agitated at 50% to an internal temperature of 182-185°C. The first vessel was then heated with fresh o-DCB (50 kg) to phosphorus. The rinse was then transferred from the Mott filter to a second vessel in the same manner. The filtrate was concentrated to 415 kg. After this, it contained 24.6 wt% solids. ICP-Dig: Sodium (3 ppm), Potassium (7 ppm) , Zinc (0ppm), Calcium (4ppm), Aluminum (0ppm), Iron (0ppm m), titanium (0 ppm), phosphorus (11 ppm), IC-extraction: sulfuric acid (4.78 ppm) , chloride (0.84ppm), phosphate (<0.5ppm), nitrate (<0.5ppm), Nitric acid (<0.5ppm).
[0048] At this point, the material is substantially free of contaminant inorganic species and is It could be used directly in condensation polymerization to prepare
[0049] The filtrate was further concentrated to 400 kg (30 wt% solids) and then transferred to the first vessel. The solution was agitated at 50% power, and then the hot oil was discharged through the valve. At 64°C, the temperature spiked to 68°C. It was noted that the crystallization had begun. After cooling to 6.5° C., the contents were visually inspected to confirm crystallization.
[0050] The slurry was then transferred to a non-heated centrifuge, which contained a Teflon filter medium. The liquid was separated from the solids by centrifugation at 90,000-1,100 rpm. After 10 minutes, the centrifuge was stopped and the cake was removed. This was continued until all solids were collected. The process was repeated for a total of four cakes of 3,3'-BPA-DA (127 kg). The white solid 3,3'- was used to estimate the abs.wt% solids of each cake. Vacuum a representative pan from each cake until a consistent mass of BPA-DA is obtained. Drying in an oven at 80-85°C. Based on this information, 87.6 kg (3,3 The estimated dry weight yield of 1.01% from 1-BPA-TA was 1.01% for the ring closure step. ICP-Dig: Sodium (2 ppm), Potassium (5 ppm), Zinc (0ppm), calcium (0ppm), aluminum (0ppm), iron (0ppm), Titanium (0ppm), Phosphorus (12ppm), IC-extract: Sulfuric acid (10.06ppm), Salt Chloride (<0.5ppm), phosphate (<0.5ppm), nitrate (<0.5ppm), nitrite (<0.5 ppm).
[0051] The vessel was charged with o-DCB (146 kg) and the 3,3'-BPA-DA ( The contents were mixed with 35.7 kg of ammonia (dry weight basis, 68.6 mol, 0.973 equivalents). Heat to 105°C with 30°C refrigeration and then add phthalic anhydride (519 g, 3.5 mol , 0.0496 equiv.) was added. The contents were kept under nitrogen overnight. The vessel was then charged with 4,4 Charge '-DDS (17.5 kg, 70.5 mol, 1 equivalent) and heat the internal temperature to 130°C. After 1 hour, the internal temperature was adjusted to 180° C. After an additional 2 hours, the stoichiometric amount Samples were taken for chemical analysis. Once the batch was mixed with 0-0.2 mol% excess Once the solution was hydrated, the material was filtered through a Mott filter (2 microns) while maintaining the solution at 180°C. The solution was concentrated to 35 wt% solids and then poured into a second vessel. The polymer solution was then extruded to form pellets. GPC: Amount average MW=55,187g / mol, Mn=24,586g / mol, PDI=2.2 4, Mz / Mw=1.47, ICP-Dig: Sodium (2.0 ppm), Potassium ( 12ppm), Zinc (2ppm), Calcium (0ppm), Aluminum (0ppm) , Iron (0ppm), Titanium (0ppm), Phosphorus (8ppm), IC-extraction: Sulfuric acid (9.7 ppm), chloride (1.8 ppm), phosphate (1 ppm), nitrate (<0.5 ppm), Nitric acid (<0.5 ppm), Tg (differential scanning calorimetry DSC): 266°C.
[0052] The purification methods for the isolated BPA-TA are described in Examples 1-5 and summarized in Table 2 below. When the mixture is agitated and hot water is used (Example 4), the mixture is stirred without stirring. Compared to washing with room temperature water (Example 1), it was significantly Less water is required. However, the centrifuge for water washing of crude BPA-TA The use of a glass fritted funnel provides a lower sulfuric acid and A better quality material having a higher glycerol content and sodium content was provided (Example 5).
[0053] [Table 3]
[0054] <Example 6> The hydrolysis vessel was charged with DI water (351 kg). The reactor was purged with nitrogen for 9 h. The mixture was agitated at 0% output. Then, a 50% NaOH aqueous solution (60.25 kg, 7 53.1 mol, 5.76 equiv.) was added. Next, N,N'-Ph-B in o-DCB was added. PA-BI (94 mol% N,N'-Ph-3,3'-BPA-BI and 4.4 mol % N,N'-3,4'-BPA-BI isomer mixture) solution (25.78 wt% solids The total mass of 340.25kg was added over 2.5 hours. Then, the contents (744k g) Set the nitrogen regulator to 10 psig and seal. The pressure was increased to 130 psig (178°C) for an additional 2 hours. 0 psig, after which the contents were cooled to 120° C. and agitated overnight. The next morning the contents were reheated to 180°C under pressure with 100% agitation. After 8 hours, the contents were cooled to 90°C and then agitated at 90% power over the weekend. The vessel was carefully depressurized to 2 psig after which a sample was taken. UPLC analysis indicated that the hydrolysis was complete.
[0055] Agitation was then stopped and the layers were allowed to separate for 2 hours. The o-DCB / aniline layer was drained, and 469.5 kg (predicted to be 474 kg) was hydrolyzed. The vessel was poured into waste until only the remaining liquid remained. It was noted that a clean separation had occurred. At this point, the upper (H2O / BPA-TA·4Na) layer (474 kg, 20 wt% solids) Then, the heated oil in the vessel was heated to 120-125℃ with 50% agitation. The holding tank was charged with DI water, which was then heated to 95°C. If necessary, send it to the hydrolysis vessel and remove the azeotropic mixture by distillation. The overhead was monitored every 30 minutes for the presence of aniline. After UPLC analysis of the flask bottoms showed no aniline present, 1 kg of material was added. The aqueous solution was then transferred from the hydrolysis vessel to a second vessel. The contents were then cooled to 67.5°C.
[0056] Charge DI water (40 kg) into the quench vessel and agitate without heat. 69.6% HNO3 aqueous solution (81.82 kg, 903.8 mol, 6.91 equivalents) The material was charged from a Teflon-lined drum pump through a PVC flexible hose. The lines were then flushed with DI water (15 kg) and cooled at 50% agitation. Then, the aqueous solution of BPA-TA·4Na (501 kg) was sent to the enchi vessel. The mixture was transferred to a quench vessel over a period of 60 minutes, followed by a rinse with DI water (35 kg). A total mass of 48 kg was given. During the transfer, the temperature rose from 67.5°C to 70°C. The milky orange-yellow mixture was then agitated slowly without heat. After a total quench time of 4.5 hours, the sample was found to be tacky. The mixture was found to be a non-volatile, free flowing yellow-orange slurry.
[0057] Using Teflon lined flexible hoses and fittings of suitable compatible construction materials. The slurry in the quench vessel is then quenched with a heated quencher containing 60 micrometer Teflon filter media. The liquid was transferred to a 40 liter Nutsche filter without a filter. The filtrate was separated from the solids in the filter and sent to a polypropylene tote. After that, the transfer process continues until the product cake fills the bottom section of the Nutsche filter. The process was then repeated. The filter was then depressurized.
[0058] Clean and fill the hold tank with DI water without heating, then 50 p sig. Water was transferred from the holding tank to the Nutsche filter to remove the product cake. The system was pressurized as before and the filtrate was pumped into a polypropylene tote. The filtrate pH was 3. The DI water washing process was repeated two more times until the combined water was above 0.5%. The system effluent was immediately neutralized to a pH of 6-9. All material from the quench vessel was collected. This isolation process was repeated multiple times until a total of 84.5% BPA-TA isomers were isolated. kg of wet cake was collected to provide near quantitative yields for hydrolysis / quenching. Some material (3.22 kg) was removed for further study. g: Sodium (109 ppm), Potassium (6 ppm), Zinc (0 ppm), Calcium Aluminum (1 ppm), Aluminum (0 ppm), Iron (0 ppm), Titanium (0 ppm), Lithium IC-Total: Sulfate (<20ppm), Chloride (3,913ppm) ), Phosphate (<20ppm), Nitrate (3,000ppm), Nitrite (497ppm), U PLC: BPA-TA isomer (97.52 mol%).
[0059] Prior to the ring closure reaction, the reactor and Mott filter were rinsed and cleaned with DI water. The reactor was then charged with o-DCB (400 kg) and then drained. The combined BPA-TA wet cake (72.78 kg dry weight basis, 130.8 mol Nitrogen was added and the mixture (14.5 wt% solids for BPA-DA) was heated. The mixture was agitated and then heated to 182-187°C to remove water and close the ring. After .5 hours, the vessel reached the target temperature. The mixture then reached a total mass of 352 kg. Allow to concentrate to 19.3 wt% solids and add fresh o-DCB as needed. At the same time, the second vessel was heated with o-DCB to maintain this level. The tube was thoroughly cleaned and drained for future use. 182°C for 5.5 hours Later, analysis showed that the ring closure was not complete. At this point, the reactor was placed in an aeration tank overnight. The next morning, the solution was diluted with fresh o-DCB for 570 min. kg to make 11.9 wt% solids. After another 7 hours, the overhead sample was The sample showed 39.1 ppm water present. UPLC analysis of the reactor contents showed that ring closure was complete. The bread solids test showed 10.65 wt% solids, indicating that B 89.2% (10.65% x 570 kg / The estimated yield was 68.07 kg (scale 1). The mixture was then heated to 120 °C. Allow to cool overnight. UPLC: BPA-DA isomers (95.58 mol%), B PA-AnhDA (2.44 mol%).
[0060] The dianhydride solution was then passed through a heated 2 micrometer Mott filter into a second vessel. to remove any residual inorganic species present, and then send it to fresh o-DCB (50 kg). The filtrate was then maintained at 182-185°C with 50% agitation. The filtrate was then concentrated to 352 kg (17-19 wt% solids). Tests showed 15.36 wt% of the bisphenol A (BPA)-TA isomers, with 79.4% (15.36% The ICP-Dig provided an estimated yield of 352 kg / 68.07 kg scale. Sodium (0.6ppm), Potassium (1ppm), Iron (2.3ppm), IC-extracted : Sulfuric acid (<0.5ppm), chloride (1.57ppm), phosphoric acid (<0.5ppm), nitrate Acid (<0.5ppm), Nitrite (<0.5ppm).
[0061] The solution was cooled to 50-55°C with 50% agitation and then held for 2 hours. The agitation of the mixture was increased to 85% and then further heated to 30-40°C. Cool overnight. Agitation was reduced to 40% and the contents were later further cooled to 17°C. After several hours, the slurry was sent to a Nutsche filter to collect the dianhydride product. Using a SL-lined flexible hose and fittings of suitable compatible materials of construction, The Lee was placed in a non-heated 40-liter Nutshell filter containing 60-micrometer Teflon filter media. At 50 psig, the liquid was separated from the solids by a Nutsche filter. After filtration was completed, the product cake was separated from the filtrate and sent to a carbon steel drum. The transfer process was repeated until the mixture filled the bottom section of the Nutsche filter. The filter was then depressurized. The filtrate was a dark orange solution, which was 0.01% based on the bread solids test. The solid content was 1.99 abs.wt%. UPLC of the filtrate revealed BPA-DA isomers and A total of five cakes were collected, each of which also showed the presence of several unknown substances. The DA isomer was obtained as a yellow solid with a yield of 46.57 kg (68.4% yield from the BPA-TA isomer). UPLC: BPA-DA isomer (96.89 mol%), BPA-A nhDA (2.95 mol%), ICP-Dig: sodium (2 ppm), potassium ( 5ppm), Zinc (0ppm), Calcium (0ppm), Aluminum (0ppm), Iron (0ppm), titanium (0ppm), phosphorus (12ppm), IC-extraction: sulfuric acid (0.5 6ppm), chloride (<0.5ppm), phosphate (<0.5ppm), nitrate (<0.5ppm) pm), nitrite (<0.5 ppm).
[0062] <Example 7> The following example used 3,3'-BPA-TA, which has the following profile: ICP-D ig: sodium (269ppm), potassium (5.6ppm), zinc (3.1ppm) , Calcium (5.4ppm), Aluminum (0ppm), Iron (0ppm), Titanium ( 0ppm), Phosphorus (5.5ppm), IC-Total: Sulfate (1,082ppm), Chloride (4,017 ppm), phosphate (<20 ppm).
[0063] Mechanical stirrer, Dean-Stark trap, condenser, and nitrogen inlet In a 250 mL three-neck round bottom flask, 3,3'-BPA-TA (26.91 g, 48 0.36 mmol) and o-DCB (142.6 g). The container was placed in a 25°C oil bath and the nitrogen flow was increased with agitation at 200 rpm. Then the temperature set was adjusted to 200° C. to concentrate the reaction.
[0064] After 1 hour and 5 minutes, 46.8 g of distillate was removed to make a .about.20 wt% solids mixture. After an additional 20 minutes, the reaction became a homogeneous yellow solution. After an additional 50 minutes, the solution became homogeneous without stirring. The mixture was allowed to cool to room temperature overnight at RT. The next morning, the mixture was heated to 90°C with agitation. The solution was reheated at 37°C and found to weigh 113.72 g (22.20 wt % solids). This solution was used in the purification method and Comparative Examples 13 and 19 below.
[0065] A portion of the 3,3'-BPA-DA solution above (15.79 g, 22.20 wt% solids, 3 0.505g dry weight was heated to 90°C and fitted with a 0.45 micron PTFE filter. After filtration, the syringe was rinsed with room temperature o-DCB (5 mL). The combined filtrates were concentrated to give 3.39 g (96.7% yield) of a yellow solid. ICP-Dig: Sodium (4.4), Potassium (6.8 ppm), Zinc (2.7 ppm) pm), calcium (14.8 ppm), aluminum (4.2 ppm), iron (7.7 ppm) pm), titanium (1.3 ppm), phosphorus (5.1 ppm), IC-extraction: sulfuric acid (18 ppm m), chloride (7.8 ppm), phosphate (<0.5 ppm), nitrate (<0.5 ppm), Nitrite (<0.5ppm).
[0066] As summarized in Table 3, highly pure BPA-TA was obtained from similarly washed BPA-TA samples. The conversion to BPA-DA was confirmed by ring closure and acid-free filtering using a 0.45-2 micrometer filter. This was achieved after filtration of the aqueous solution. This indicates that the use of a filter is sufficient to obtain highly pure BPA-DA. For small-scale procedures, the 0.45 micrometer filter (Example 7) also works well. It was effective at
[0067] [Table 4]
[0068] <Comparative Example 8> A Parr reactor was charged with aq. sodium hydroxide (42.17 g, 50% by weight, 527.2 m mol, 5.5 equiv.), water (212 g, 212 mL), and N,N'- in o-DCB Ph-3,3'-BPA-BI (204.95g, 31.367% by mass, 95.85mm The reactor was sealed and degassed with nitrogen 10 times, then 1 The mixture was heated to 80°C (135 psig). After 45 minutes, the internal pressure was 123 psig (18 The temperature was increased to 183°C, which increased the internal pressure to 142 psig. The temperature was finally adjusted to 182°C and after 3 hours the reactor was cooled to 80°C. After carefully depressurizing the Parr reactor, UPLC analysis of the mixture showed that all of the starting material had been consumed. This shows that it has been done.
[0069] The mixture was then poured into a separatory funnel and the layers separated within 2 minutes. The colorless organic layer was removed. The yellow-orange aqueous layer containing 3,3'-BPA-TA·4Na was discarded. The aqueous layer was replaced with fresh o- The aniline was removed by washing with DCB (7×200 mL). After each wash, the layer was stirred for 2 min. After the sixth wash, only traces of aniline were present. After the seventh wash, No aniline was detected.
[0070] After standing overnight at 25° C., the aqueous solution remained homogeneous. The solution was passed through a medium frit. Filter 350 mL of the filtrate through a glass funnel to remove the very small black flake layer. The filtrate was used directly in the one-pot quench / ring closure process described below.
[0071] Mechanical stirrer, Dean-Stark trap, condenser, and dropping funnel Into a 500 mL three-neck round bottom flask was added nitric acid (57.3 g, 69.6 wt%, 632. 7 mmol) and water (50 g) were charged and then heated to 90°C. The room temperature solution was placed in a dropping funnel (350 mL of solution) and then added dropwise over a period of 1 hour. nitric acid was added. Additional water (30 mL) was used to rinse the addition funnel and add the quench vector. The mixture was then heated in an oil bath at 130° C. with a positive nitrogen flow. After 5.5 hours, the water and HNO3 were removed by distillation with H2O / HNO3 (368 g). The fraction was drained through a Dean-Stark trap. A pH of 1 was measured for the distillate. It was determined.
[0072] Next, o-DCB (250 mL, 325 g) was charged into the flask and the temperature was raised to 145°C. After 75 minutes, the temperature was increased to 160°C and additional oD CB (50 mL, 65 g) was added. After another 75 min, the distillate (156.6 g = 65 g 1.6 g of o-DCB) was drained from the trap. It was observed that the mixture contained a yellow-orange solution with a precipitate (NaNO3). .
[0073] After a total of 3 hours at 160° C., the distillate of o-DCB (85 g) was drained. UPLC analysis showed that the ring-closure reaction was complete. The mixture had a small amount of solids. The solution was concentrated further over 1 h 45 min and then added o-DCB (58 g) was drained from the trap. At this point, the solution appeared dark orange-brown. However, UPLC analysis showed no significant change in product purity.
[0074] The concentration was increased to 20 relative wt% solids [BPA -DA / (BPA-DA+o-DCB)]. After cooling to 120° C., the mixture The solids were filtered through a fine frit (4-5.5 micrometer) glass funnel. The yellow solid was then rinsed with o-DCB (50 mL, 65 g) at 120° C. The mixture was agitated with DCB (50 mL, 65 g) at 120° C. and refiltered. The dark amber filtrate (311.28 g) was found to be 14.44 wt% solids by pan solids test. The calculated dry weight yield was 44.95 g (3-sulfuric acid from the bisimide). >90.10% yield by UPLC. UPLC: BPA-DA isomers + BPA-AnhDA ( 98.63%), ICP-Dig: Sodium (111), Potassium (12 ppm), Nitrogen Lead (9.4ppm), calcium (8ppm), aluminum (2ppm), iron (5.1 ppm), titanium (0 ppm), phosphorus (13.2 ppm), IC-extraction: sulfuric acid (<0.5 ppm), chloride (<0.5ppm), phosphate (<0.5ppm), nitrate (<0.5ppm m), nitrite (<0.5 ppm).
[0075] <Example 9> In a Parr reactor, pure N,N'-Ph-3,3'-BPA-BI (30 g, 44.7 3mmol, 1 equivalent), 50%aq.NaOH (19.68g, 50% by mass, 246.0 The mixture was charged with 100 mmol, 5.5 eq., and water (98.6 g, 98.6 mL). The mixture was briefly stirred with a glass rod to form a slurry, which was then sealed and degassed with nitrogen 10 times. Then it was heated to 180°C (135 psig). After 1 hour, the internal pressure was 135 psig. sig (180° C.). After 3 hours at this temperature, the reaction was cooled to 70° C. UPLC analysis of the homogeneous light yellow solution indicated that the reaction was complete. The crude reaction was then transferred to a separatory funnel and rinsed with water at 25°C. The mixture was washed multiple times with ethyl acetate (EtOAc) at 25° C. until the It was observed that the color of both the aqueous and organic layers changed significantly during the washing procedure.
[0076] The wash studies showed that all aniline was washed with 250 mL (4 washes) of EtOAc. This scale (28.82 g of 3,3'-BPA-TA·4Na) The final 3,3'-BPA-TA 4TA aqueous solution was blue-purple in color. C analysis showed it contained 98.98% BPA-TA isomers.
[0077] Mechanical stirrer, Dean-Stark trap, condenser, dropping funnel, and In a separate 500 mL three-neck round bottom flask equipped with a nitrogen inlet, add hydrochloric acid (28.8 g, 37.4 %, 295.2 mmol, 6.6 equivalents) and water (17 g). The solution was heated to 90°C. A homogeneous blue-purple aqueous solution of 3,3'-BPA-TA·4Na (2 10 mL, 44.73 mmol) was placed in a dropping funnel at 25 °C and the acid quench solution was added dropwise. After 50 minutes, the addition was complete. The mixture was filtered to contain a light purple solid. The resulting slurry was filterable. It was not isolated. Lee was taken directly for the ring-closing reaction.
[0078] The cloning of 3,3'-BPA-TA (44.73 mmol) containing HCl and NaCl The thick aqueous slurry was then heated in an oil bath set at 120° C. to dissolve the mixture. The mixture was concentrated. A large amount of water was distilled off and a pH of 1 was measured. After 3.25 hours, the mixture was Cool to 25°C. Heat the oil bath to 185°C for further concentration. After draining the Dean-Stark trap, the total distillate volume (pH = 1) was o-DCB (300 mL) was added to the reaction flask and heating was continued. After removing 134 mL of o-DCB, only o-DCB was overhead, and the solvent exchange The process was complete. Additional o-DCB (177 mL) was added to give a homogeneous tan solution. I made the liquid.
[0079] The contents were heated at reflux for an additional 5 hours. UPLC analysis showed that 3,3'-BP This shows that the ring closure to form A-DA is complete. The solution was then heated to 110°C. Cool and then hot filter through Whatman #1 filter paper to remove most of the NaCl. The filtrate was filtered through a fine frit (4-5.5 micrometer) glass funnel at 110 °C. The off-white solids were combined and washed with o-DCB at 25°C. The filtrate (250 mL, 318.71 g) appeared yellow-brown in color. It was determined that the '-BPA-DA / o-DCB solution was 6.96 wt% solids. Therefore, the calculated dry weight yield was 3-sucrose from N,N'-Ph-3,3'-BPA-BI. The yield was 22.18g (95.3%) in the step. UPLC: BPA-DA isomers + BPA -AnhDA (99.66%), ICP-Dig: Sodium (0), Potassium (12p pm), zinc (13 ppm), calcium (10 ppm), aluminum (1 ppm), Iron (9.5ppm), titanium (0ppm), phosphorus (22ppm), IC-extraction: sulfuric acid (< 0.5ppm), chloride (2.47ppm), phosphate (<0.5ppm), nitrate (0.8 7ppm), and nitrite (<0.5ppm).
[0080] The purification methods of Comparative Example 8 and Example 9 are summarized in Table 4 below. The intermediate was quenched with either nitric acid (Comparative Example 8) or hydrochloric acid (Example 9) to obtain BPA. The tetraacid product was not isolated but was directly ring-closed in o-DCB to give BP A-DA was formed. Excess nitric acid and hydrochloric acid were distilled off during the process. Filtration using a glass funnel alone (Comparative Example 8) was superior to that of Motof in removing sodium. Filtration through a filter (Examples 5 and 6) or through filter paper in a fine fritted glass funnel It was observed that the method was not as effective as the previous method (Example 9).
[0081] [Table 5]
[0082] Example 10a Culture tubes were filled with 3,3'-BPA-DA (2.6 g, 5.0 mmol) and o-DCB (8 1 mL) to make a 20 wt% solids mixture, then stir until a homogenous solution is formed. The flask was heated to 85° C. with an oil bath. A stock of H2SO4 in DI water was added to the volumetric flask. A solution (95%, 103 mg, 1.03 mmol) was prepared to make a 50 mL solution. In a 2 volumetric flask, add a stock solution of NaHCO3 (42 mg, 0.50 mM) in DI water. ol) was prepared to make a 25 mL solution. In the culture tube, add 2.5 mL of aq. NaHCO3 stock solution (4.2 mg dry wt, 0.05 mmol, 1 mol%) and 2.5 mL of aq. H2SO4 stock solution (4.90 m g dry wt, 0.05 mmol, 1 mol%) was added. The mixture was stirred for 8 h with vigorous stirring. The mixture was heated at 5°C and samples were taken every hour to monitor the formation of BPA-TA (a ring-opening product). After 6 hours, UPLC analysis indicated the following species were present: BPA-D A (36.6%), BPA-TA (47.5%), and BPA-diacid anhydride.
[0083] Example 10b Culture tubes were filled with 3,3'-BPA-DA (2.6 g, 5.0 mmol) and o-DCB (8 1 mL) to make a 20 wt% solids mixture, then stir until a homogenous solution is formed. The flask was heated to 85 °C in an oil bath. A stock solution of H2SO4 in DI water was added to the volumetric flask. A 50 mL solution was prepared by preparing a 50 mL solution of 103 mg of 95% ethyl acetate (1.03 mmol). In a volumetric flask, add a stock solution of NaHCO3 (462 mg, 5.5 mmol) in DI water. l) was prepared to make a 25 mL solution. To the tube, add 2.5 mL of aq. NaHCO3 stock solution (46.2 mg dry wt, 0.5 5 mmol, 11 mol%) and 2.5 mL of aq. H2SO4 stock solution (4.9 0 mg dry wt, 0.05 mmol, 1 mol%) was added. The mixture was stirred vigorously. The mixture was heated at 85° C. with samples taken every hour to measure the formation of BPA-TA (a ring-opened product). After 6 hours, UPLC analysis indicated the following species were present: BPA. -DA (79.6%), BPA-TA (5.3%), and BPA-diacid anhydride.
[0084] <Example 10c> Culture tubes were filled with 3,3'-BPA-DA (2.6 g, 5.0 mmol) and o-DCB (8 1 mL) to make a 20 wt% solids mixture, then stir until a homogenous solution is formed. The flask was heated to 85 °C in an oil bath. A stock solution of H2SO4 in DI water was added to the volumetric flask. A 50 mL solution was prepared by preparing a 50 mL solution of 103 mg of 95% ethyl acetate (1.03 mmol). In a volumetric flask, add a stock solution of NaHCO3 (1.385 g, 16.5 ml) in DI water. mol) was prepared to make a 25 mL solution. In a culture tube, add 2.5 mL of aq. NaHCO3 stock solution (138.5 mg dry wt, 1 .65 mmol, 33 mol%) and 2.5 mL of aq. H2SO4 stock solution (4 0.90 mg dry wt, 0.05 mmol, 1 mol%) was added. The mixture was stirred vigorously. The mixture was heated at 85°C with 0.01% CO and samples were taken every hour to measure the amount of BPA-TA (ring-opened product). Formation was monitored. After 6 hours, UPLC analysis indicated the presence of the following species: B PA-DA (97.9%), BPA-TA (0%).
[0085] The effect of NaHCO3 concentration on the ring opening of BPA-DA investigated in Examples 10a-c The effect is further illustrated by Figure 2, where 1 mol% (0.01 equiv.) ) only in 3,3'-BPA-DA solution with NaHCO3 (containing 1 mol% H2SO4 It was found that treatment with 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether) resulted in significant amounts of ring-opened products after only 1 hour. Washing with more than 8 mol% (0.08 equiv.) NaHCO3 in water has no effect on product quality. Up to 3 hours of cleaning time was allowed without any significant impact on the Wash the 3,3'-BPA-DA solution with more than l% (0.22 equivalents) NaHCO3 The results showed little or no evidence of ring opening after 23 hours of mixing time. 3,3'-BPA-DA solutions showed no evidence of ring opening when in contact with DI water for up to 2 hours. However, when the contact time exceeded 4 hours, BPA-Anh A significant amount of BPA-DA degradation to DA and BPA-TA was observed. showed that the use of stronger bases such as Na2CO3 or NaOH was ineffective. Because a significant amount of ring opening was observed, the inventors therefore concluded that Unexpectedly, a specific set of washing conditions was required to avoid decomposition of the desired product. We discovered that this is possible.
[0086] <Example 11> The following procedure used 3,3'-BPA-TA with the following profile: ICP-D ig: sodium (72 ppm), potassium (4.4 ppm), zinc (0.5 ppm), Calcium (4.8 ppm), Aluminum (9.3 ppm), Iron (3.8 ppm), Tantalum (0ppm), Phosphorus (7.4ppm), IC-Total: Sulfuric acid (542ppm), Salt phosphate (<20ppm), nitrate (<20ppm), nitrite (<2 0 ppm).
[0087] 250mL with magnetic stir bar, Dean-Stark trap, and condenser In a two-neck round-bottom flask, add ground 3,3'-BPA-TA (10 g, 17.97 mmol) , 1 equivalent), aq. sulfuric acid (0.1762g, 0.08985mmol, 0.5mol%, 0.005 equivalents, 881 ppm relative to 3,3'-BPA-TA), and o-DCB ( The flask was then placed under nitrogen and heated to 185°C. After 40 min, the distillate (25 mL) was drained from the Dean-Stark trap. The cycle time was 2 h, and fresh o-DCB (25 mL) was added to the reaction flask. Afterwards, a homogeneous yellow-green solution was observed. UPLC analysis indicated the reaction was 99.82% complete. The mixture was removed from the heat and the remaining distillate (31 mL) was poured into a trap. The pan solids test indicated that the reaction mixture was 9.95 wt% solids. (total mass present was 93.97g).
[0088] The reaction mixture (88.01 g, 9.95 wt% solids) was heated to 85°C in a 1 L beaker. Upon heating, a homogeneous olive to orange solution was produced. A saturated aqueous solution of sodium bicarbonate ( 8.25 wt%, 9 g NaHCO3 / 100 g water) was heated to 85°C in a separate beaker. Add aq.NaHCO3 solution (60mL) to the reaction solution and heat thoroughly for 30 seconds. After agitation was discontinued, the layers separated within 1 minute. The upper aqueous layer was yellow-orange. The bottom organic layer became a lighter yellow solution while the bottom organic layer darkened to a yellow color (still pH=9). Agitation at 85°C was continued for 3 hours to follow the decomposition of the product. The aqueous sample showed traces of BPA-TA isomers at 2.978 min and traces of unknowns. A sample of the organic layer showed pure BPA-DA isomers and BPA-diacid anhydride.
[0089] The layers were separated and the organic layer was washed with water (3×60 g) at 85° C. for 3 min each. After the first water wash, sodium The sodium content was reduced from 10,000 ppm to 30 ppm. Subsequent washings reduced the sodium content The concentration was further reduced to 8 ppm and 4 ppm. The final organic layer was hot plated in a beaker. The mixture was concentrated further by ethanol to eliminate water. The solution weighed 57.75 g and had a concentration of 11.99 wt% solids (bread solids). Based on the 88.01 g solution used in the cleaning study, the yield was 79.07%. UPLC: BPA-DA isomers + 3,3'-BPA-AnhDA (9 8.81%), ICP-Dig: Sodium (1.6 ppm), Potassium (5.8 ppm) ), zinc (1.8ppm), calcium (10ppm), aluminum (0ppm), iron (2.3ppm), titanium (0ppm), phosphorus (15ppm), IC-extraction: sulfuric acid (2. 4ppm), chloride (<0.5ppm), phosphate (<0.5ppm), nitrate (<0.5ppm) pm), nitrite (<0.5 ppm).
[0090] <Example 12> The following procedure used 3,3'-BPA-TA with the following profile: ICP-D ig: sodium (274ppm), potassium (2.7ppm), zinc (1.5ppm) , Calcium (3.2ppm), Aluminum (0ppm), Iron (7.7ppm), Titanium Nitrogen (0 ppm), Phosphorus (8.3 ppm), IC-Total: Sulfuric acid (1,208 ppm), Chloride (671 ppm), phosphate (<20 ppm), nitrate (530 ppm), nitrite (1 28 ppm).
[0091] Equip the flask with a mechanical stirrer and Dean-Stark trap / condenser under nitrogen. In a 2 L three-neck round-bottom flask, add 3,3'-BPA-TA (200 g, 281 mmol, 7 Coarsely ground wet cake (8.30 wt%) and o-DCB (1044 g, 803 mL) The mixture was then placed in an oil bath and heated to 182°C. After 3h15min, The N-Stark trap was drained (369.23 g = 43 g H2O + 326.23 g of o-DCB). Additional o-DCB (100 g) was then added to the reaction and heating was continued. After 2 hours, more distillate (141.56g = 1g H2O + 140.56g Drain the o-DCB from the trap and add additional o-DCB (100 g) to obtain a homogenous light yellow eluate. The reaction solution was added to the reaction mixture. UPLC analysis showed that the ring closure was complete and all of the tetraacid had been consumed. The solution had a total mass of 933 g and contained 15.7 wt% solids. It was roughly estimated that.
[0092] The contents were further concentrated and additional distillate (203.81 g) was drained to give a 20 wt. % A solids solution was made. The reaction was then allowed to cool to 25°C. 695g The total mass was obtained and the bread solids showed it to be 21.27 wt% solids. The solution was reheated to 85°C and 2.2 wt% aq. NaHCO3 (350 g, preheated to 85°C) was added. After agitation was stopped, the layer was washed for 10 to 15 minutes. The phases separated within 2 minutes. The aqueous layer was red-orange and the organic layer appeared to have a lighter orange color than before. The organic layer was then washed with H2O (350 g) at 85 °C for 2 min. After agitation was discontinued, the layers again separated within 2 min. The organic layer was washed with water (10 mL each). After one water wash, the sodium content was reduced from 4,000 to Subsequent washes reduced the sodium content to 60, 20, and 10 ppm. After washing, the orange organic solution (660.39 g) was mechanically 4-neck 2 L with stirrer, Dean-Stark trap, condenser, and nitrogen The dianhydride solution was reheated to reflux to drive off residual water. After all the water had distilled off, a similar amount of o-DCB was added back to the vessel. The solid content was 22.17 wt% of 3,3'-BPA-DA in a bright orange solution (658.5 g). The calculated yield was 99.7% (145.99 g dry weight). ) UPLC: BPA-DA isomers + BPA-AnhDA (97.4%). IC P-Dig: Sodium (1.7 ppm), Potassium (6.8 ppm), Zinc (10.3 ppm) ppm), calcium (14.5ppm), aluminum (0ppm), iron (1.1ppm m), titanium (0 ppm), phosphorus (16 ppm), IC-extraction: sulfuric acid (0.56 ppm) , chloride (<0.5ppm), phosphate (<0.5ppm), nitrate (<0.5ppm), Nitric acid (<0.5ppm).
[0093] <Comparative Example 13> The following comparative example used the 3,3'-BPA-DA solution prepared in Example 7.
[0094] 3,3'-BPA-DA solution (41.08 g, 22.20 wt% solids, 9.120 g A portion of the dry weight was heated to 90°C and saturated aqueous sodium bicarbonate solution (30 mL) at 90°C was added. The contents were shaken for 1 min and then the layers were allowed to separate over 2 min. The aqueous layer was removed and measured to have a pH of 10. The organic layer was reheated to 90 °C, again placed in a separatory funnel, and diluted with 90 °C deionized water (2 × 30 mL). ) for 1 min. The layers were allowed to separate for 2 min before separation. The organic layer was concentrated to give 8.50 g (93.2% yield) of a yellow solid. Thorium (127), potassium (10.1 ppm), zinc (2.6 ppm), calcium (15ppm), aluminum (2.5ppm), iron (10.6ppm), titanium (1. 3ppm), phosphorus (7.5ppm), IC-extraction: sulfate (6.5ppm), chloride (8. 6ppm), phosphate (<0.5ppm), nitrate (<0.5ppm), nitrite (<0.5ppm) pm).
[0095] The purification methods of Examples 11 to 13 are summarized in Table 5. The BPA-TA intermediate was purified by o-DCB. The ring is closed by catalytic amount of acid to prepare BPA-DA. The homogeneous dianhydride solution is washed with water to remove ionic species. The up-water wash removes residual sodium bicarbonate from the organic layer. and sulfuric acid (from the sulfuric acid quench of the tetrahydrofuran acid) are removed to levels below 3 ppm. In Comparative Example 13, washing with a saturated aqueous sodium bicarbonate solution removed almost all of the sulfuric acid and chloride. However, insufficient water was used for follow-up cleaning. When the mixture is cooled, sodium may remain as a contaminant in the form of sodium bicarbonate. do.
[0096] [Table 6]
[0097] <Example 14> N,N'-Ph-BPA-BI in o-DCB (93.55 mol% N,N'-Ph- 3,3'-BPA-BI and 5.73 mol% N,N'-3,4'-BPA-BI isomers A solution of 25.78 wt% solids (350 kg) of DI water (383 kg) was added to the The reactor was agitated at 90% power with a nitrogen purge for 90-120 minutes. Heating was continued until the internal temperature reached 95° C. Then, 50% aqueous NaOH (65.73 kg) was added. , 821.6 mol, 6.11 eq.) was added to V-106. Then, the contents (799 kg) with a nitrogen regulator set to 10 psig and sealed until the internal pressure was 135p The mixture was heated over the next 3 hours until the temperature reached 180°C. The pressure was maintained at 135 psig for an additional 6 hours, and then the contents were heated to 85-90°C. The vessel was then carefully depressurized to 2 psig, after which the stoichiometric A sample was taken for theoretical determination. UPLC analysis showed that the bisimide (4.3 mol%) was still present. As a result, additional 50% NaOH aqueous solution (5 0.45 kg, 68.13 mol, 0.51 eq, 6.62 eq total) was added to the mixture. (Total 804 kg). Set the nitrogen regulator to 10 psig, seal the contents, and The mixture was then reheated over the next 3 hours until the bottom pressure reached 135 psig (180°C). The pressure was maintained at 135 psig with agitation for an additional 3 hours, and then the contents were The mixture was cooled to 85-90°C. The reactor was then carefully depressurized to 2 psig and mixed. A UPLC sample of the mixture showed that hydrolysis was complete.
[0098] Stop agitation and allow the layers to mix for 90 minutes while maintaining an internal temperature of 85-90°C. The lower (o-DCB / aniline) layer was drained within 20 min and allowed to separate. The reaction vessel was then poured into the upper (HO) The reactor temperature was then increased to 100°C / BPA-TA·4Na) layer containing 19.4 wt% solids. The oil was heated to 140℃ (internal temperature 120-125℃) with 50% agitation. .
[0099] Charge the hold tank with DI water, which is then heated to an internal temperature of 95°C and, if necessary, The azeotropic mixture is then separated by distillation in the hydrolysis vessel, and the remaining 400 kg of the reactor is then separated by distillation in the hydrolysis vessel. The weight (25.5abs.wt% solids) was maintained. The overhead was aniliated every 30 minutes. The agitation was reduced to 20% power and the The oil was reduced to 120°C. UPLC analysis of the reactor bottoms showed only 0.13 mol% Removal of the aniline by-product was deemed sufficient when aniline was shown to be 360 kcal / kg. g of DI water was used for the azeotropic removal of aniline. Additional DI water (50 kg) was added to the vessel. (total mass 453 kg) to keep the BPA-TA·4Na dissolved. A sample (3.151 kg) was removed for further study. 96% (21.34% x 10.34%) from bisimide, revealing .34 abs. wt% solids. The solution was then poured into a second vessel, which provided an estimated yield of 453 / expected 100.76 kg. The mixture was transferred to a flask and maintained at 90°C with agitation.
[0100] The quench vessel was charged with DI water (84 kg) and agitated without heat. Then, add 50% H2SO4 aqueous solution (96.00 kg, 489.4 mol, 3.820 equiv.) The material was charged from a Teflon-lined drum pump through a PVC flexible hose. The lines were then flushed with DI water (15 kg) and cooled at 50% agitation. The quench vessel was then heated to an internal temperature of 90°C. From the content of the vessel (450 kg, 82.6 kg dry weight BPA- TA·4Na) was transferred to the quench vessel over 45 min. The vessel was then filled with DI water ( 35 kg) and the rinse was sent to the quench vessel as well (at 90°C). Then, gradually increase the agitation of the white slurry to 80%. After a total quench time of 2 hours, the quench vessel was heated to an internal temperature of 78°C. The oil was then cooled to 35°C and the hot oil was then drained through the valve. At this point the sample was tacky. The mixture was found to be a non-volatile free flowing white slurry.
[0101] Using Teflon lined flexible hoses and fittings of suitable compatible construction materials. , from the quench vessel containing 60 micrometer Teflon filter media without heating The slurry was transferred to a 40 liter Nutsche filter. At 50 psig, the liquid was filtered through the Nutsche filter. The solids were separated by a filter and the filtrate was sent to a polypropylene tote. It was noted that the filtrate was a clear and colorless liquid with a pH value of 1.08. After filtration is complete, the product cake is allowed to fill the bottom section of the Nutsche filter. The transfer process was then repeated. The filter was then depressurized.
[0102] Water is then transferred from the hold tank to a Nutsche filter at 50 psig, The product cake was washed. The system was pressurized as before and the filtrate was sent to a polypropylene tote. The DI water washing process was repeated two more times until the filtrate pH was above 3. This isolation process was repeated until all material from the quench vessel was collected. A total of 90.05 kg of wet cake of BPA-TA isomers was collected (65.68 kg dry weight), providing an estimated yield of 92.1% for the hydrolysis / quench step. CP-Dig: Sodium (108), Potassium (6 ppm), Zinc (1.4 ppm), Calcium (3ppm), Aluminum (0ppm), Iron (5ppm), Titanium (0ppm) m), phosphorus (6.3 ppm), IC-total: sulfate (825 ppm), chloride (728 ppm). ppm), phosphate (<20 ppm), nitrate (1,409 ppm), nitrite (231 ppm) ).
[0103] The reactor was charged with the combined BPA-TA wet cake (65.68 kg dry weight basis, 11 Both o-DCB (8.0 mol) and o-DCB (348 kg) were charged. Nitrogen was added and the mixture ( BPA-DA (15 wt% solids) was added by agitation, and then the reactor was heated. The oil was heated to 200-205°C to remove water and close the ring. Then, the mixture was cooled to 41°C. Concentration was allowed from 4 kg to 312 kg total mass (20 wt% solids). This level was maintained by adding fresh o-DCB as needed. After 6 hours Pan solids analysis showed 18.33 wt% solids, and UPLC analysis indicated complete ring closure. The mixture was then further diluted to 290 kg (20 wt% solids). It was concentrated and cooled to 83-85°C with agitation.
[0104] DI water (181 kg) with agitation in the holding tank, then sodium bicarbonate (6.94 kg) was charged to prepare a 3.7 wt% NaHCO3 aqueous solution. The BPA-DA solution was heated to an internal temperature of 83-85°C. During a short interruption, a portion of the aq. bicarbonate solution (125 kg) was transferred to the vessel. The two-phase mixture (total mass 422 kg) was agitated at 90-100% output for 30 minutes. The internal temperature was maintained at 83-85°C while the mixture was being cooled. After a few minutes, a sample was taken and the top The layer was measured to have a pH of 8.25. Agitation was discontinued and the layer was allowed to settle for 45 minutes. The bottom layer, containing the BPA-DA isomers in o-DCB, was separated by a second Transfer the mixture to the second vessel and agitate until the level in the first vessel drops to 128.5 kg. The internal temperature was maintained at 83-85°C with the addition of ethanol. The remaining upper aqueous layer was then drained to waste. The empty first vessel was then rinsed and cleaned with DI water. At this point, the total content of the second vessel was determined to be 290 kg. It was.
[0105] Drain the aq.NaHCO3 from the hold tank and then rinse with DI water. Then, DI water (187 kg) was charged and the temperature was kept at 83-85°C. The contents of the second tank were then mixed with the contents of the first tank with agitation. The mixture was then transferred to a holding tank and heated to an internal temperature of 83-85°C. (125 kg) was also transferred to the first tank for a total vessel weight of 412.5 kg. The two-phase mixture was then agitated at 90-100% power for 25 min. A sample was taken and the upper aqueous layer was determined to have a pH of 3.0. Agitation was discontinued and the layers were allowed to separate for 1 hour. The light yellow lower (organic) layer was again poured into the second vessel until the mass in vessel 1 was reduced to 131 kg. At this point, the mass in the second vessel was observed to be 297.5 kg. The slurry content of the second vessel was heated to an internal temperature of 83-85°C with agitation. The remaining aq. cleaning solution was pumped through the bag filter to a waste tote. Examination of the filter revealed several kilograms of trapped BPA-TA cake. The vessel in step 1 was rinsed and cleaned with DI water and then drained. After this, the material in the second vessel was washed with the collected BPA-TA capsule from the bag filter. The mixture was then transferred again to the first vessel together with the syrup, and the vessel was heated to 83-85°C with agitation. The second vessel was also replenished with additional o-DCB (50 kg). The second vessel was then washed with water and transferred to the first vessel in the same manner. Finally, the second vessel was washed with water and transferred to a new oD Rinse and clean with CB and drain.
[0106] Before Mott filtration: ICP-Dig: Sodium (321), Potassium (6 ppm), Zinc (2ppm), calcium (3ppm), aluminum (0ppm), iron (10ppm) , titanium (0ppm), phosphorus (9ppm), IC-extraction: sulfuric acid (101.2ppm), salt Chloride (0 ppm), phosphate (0 ppm), nitrate (0 ppm), nitrite (0 ppm).
[0107] Prior to Mott filtration, the second vessel was heated until the internal temperature reached 95-105°C. The mixture was prepared by heating. Heat the oil in the first vessel to 200-205℃ with 40% agitation. Any species present were ring-closed. The contents were then concentrated to 267 kg (23 wt% solids). After this, an overhead sample indicated that 0 ppm water was present. Pan solids revealed the solution to be 18.51 wt% solids. At this time, the vessel was measured to weigh 278 kg. UPLC analysis showed that there was PA-DA isomers and trace amounts of 3,3'-BPA-dianhydride (3,3'-BPA-An Therefore, while cooling the solution to an internal temperature of 95-105°C, The micrometer Mott filter was heated to 95-105°C. The contents were then The filter is then passed to a second, clean vessel to remove any residual inorganic The seeds were removed. The filtrate was then stirred at 50% agitation until the internal temperature was maintained at 95-105°C. The first vessel was then rinsed with fresh o-DCB (60 kg) and rinsed. The filtrate was then transferred from the Mott filter to a second vessel. A sample (332 kg total vessel weight) was taken and found to be 15.93 wt% solids. The estimated yield for the ring-closing step was 86.1% (15.93% × 332 kDa). Finally, the filtrate was diluted to 320 kg (17.32 wt% solids). The mixture was concentrated to 100 ml.
[0108] After Mott filtration: ICP-Dig: Sodium (111), Potassium (6 ppm), Zinc (3ppm), calcium (3ppm), aluminum (1ppm), iron (6ppm), Titanium (0ppm), Phosphorus (10ppm), IC-extraction: Sulfuric acid (20.1ppm), Chloride (<0.5ppm), phosphate (<0.5ppm), nitrate (<0.5ppm), nitrite ( <0.5 ppm).
[0109] A concentrated solution of BPA-DA isomers in o-DCB was incubated for 25 min with increased agitation. Cool to an internal temperature of 40° C. and hold for 2 hours, after which visual inspection revealed no crystallization. The slurry was then heated to an internal temperature of 58-60°C. Teflon lined flexible hose and suitable compatible materials of construction. The slurry was then filtered through a non-heated filter containing 60 micrometer Teflon filter media. The liquid was transferred to a 40 liter Nutsche filter. The solids were separated by a filter and the filtrate was sent to a carbon steel drum. After that, the transfer process continues until the product cake fills the bottom section of the Nutsche filter. The filter was then depressurized and the cake removed. All product solids were removed. This isolation process was repeated until 49.4 kg (BPA-T) was collected. The product was collected as a white solid (80.4% yield from the A isomer). The overall yield of the dianhydride was calculated to be 74.1%. Sex + BPA-AnhDA (100%), ICP-Dig: Sodium (18 ppm), Potassium (6ppm), zinc (1ppm), calcium (1ppm), aluminum (0 ppm), Iron (0 ppm), Titanium (0 ppm), Phosphorus (10 ppm), IC-extracted: Sulfur Acid (6.14ppm), Chloride (31.51ppm), Phosphate (<0.5ppm), Nitric Acid (<0.5ppm), nitrite (<0.5ppm).
[0110] <Example 15> N,N'-Ph-BPA-BI (93.09 mol% N,N') in o-DCB at 80 °C -Ph-3,3'-BPA-BI and 4.38 mol% N,N'-3,4'-BPA- A hydrolyzed mixture of BI isomers (28.74 wt% solids, 293 kg total mass) DI water (292 kg) was added to the digestion vessel. The reactor was maintained at 90% with a nitrogen purge. Then, 50% NaOH aqueous solution (55.24 kg, 690 0.5 mol, 5.5 equiv.) was added to bring the total reactor mass to 641 kg. The cell was sealed with a nitrogen regulator set at 10 psig. The internal pressure was 122 p.s.i. The contents were heated until the temperature reached sig (171-172°C). Pressure was reduced with agitation. The pressure was maintained at 120 psig for an additional 6 hours, and the contents were then cooled to 85-90°C. The vessel was carefully depressurized to 2 psig after which a stoichiometric sample was taken. UPLC analysis showed that the orange aqueous layer contained only BPA-TA, aniline, and trace impurities. This indicates that while the white organic layer still contains traces of BPA-BI. did.
[0111] Additional 50 wt% aq. NaOH (5.02 kg, 62.7 mol, 0.50 equiv., total A total of 6.0 equivalents were charged. The reactor was sealed as before, and then The mixture was heated to 120 psig (172°C) with stirring. After an additional 4 hours, the contents were cooled to 90°C and held overnight. Safely depressurized to 2 psig. A second stoichiometric sample was taken after 10 min. UPLC confirmed that hydrolysis was complete. The agitation was stopped and the water layer was still orange. 416.5 kg (predicted 413 kg) was allowed to separate in the hydrolysis vessel. The bottom (o-DCB / aniline) layer was removed to waste until a clean separation occurred. At this point, the upper (H2O / BPA-TA 4Na) layer (41 The hot oil from the hydrolysis vessel was then poured into a 1000 ml container. The mixture was heated to 120-125°C with 50% agitation.
[0112] The hold tank was charged with DI water, which was then transferred to the hydrolysis vessel as needed. The overhead was sent to the 413 kg weight while the azeotrope was separated by distillation. The presence of aniline was monitored every 30 minutes. A total of 337 kg of water was held. After being removed from the tank, overhead analysis showed only 15 ppm aniline present. The contents of the hydrolysis vessel (404 kg) were then stirred overnight with agitation. The next morning, the solution was transferred to a second vessel and heated to 85°C with agitation. The temperature was maintained at 90°C.
[0113] The quench vessel was charged with DI water (81 kg), agitated, and then cooled for 50 A 100% H2SO4 aqueous solution (81.26 kg, 414.3 mol, 3.3 equivalents) was added to a PVC frame. The feed was delivered to the addition hopper from a Teflon-lined drum pump by a flexible hose. The transfer line was then flushed with DI water (15 kg) and transferred to the quench vessel. The vessel was then heated to 85-90°C with 50% agitation. The aqueous solution of BPA-TA·4Na was transferred to the quench vessel over 45 min and then washed with DI water ( 40 kg) to give a total mass of 615 kg. While heating to 95°C, the agitation speed was gradually increased to 80% output. After 10 minutes, the mixture was too viscous to collect samples. The content was then increased to 90% and the contents were held at 90° C. for another 2 hours. After this, the samples The mixture was found to be a non-sticky, free-flowing, white suspension. The hot oil was drained through the valve and the contents were allowed to cool overnight prior to filtering. After 2 hours, the internal temperature reached 69° C. and the slurry was ready to be filtered.
[0114] Using Teflon lined flexible hoses and fittings of suitable compatible construction materials. From the quench vessel, a 40 liter nut containing 60 micrometer Teflon filter media was The slurry was transferred to the Nutsche filter. At 50 psig, the liquid was transferred to the Nutsche filter. The filtrate was separated from the solids and sent to a polypropylene tote. The transfer process is repeated until the product cake fills the bottom section of the Nutsche filter. The filter was then depressurized.
[0115] Clean and fill the hold tank with DI water and heat to 80-85°C. It was then pressurized to 50 psig. Water was then pumped from the hold tank to the Nutchefill. The product cake was washed by transferring it to a polypropylene toner. The system was pressurized as before and the filtrate was poured into a polypropylene toner. The DI water cleaning process was repeated a second time. The combined aqueous waste The solution was immediately neutralized to a pH of 6-9. This was continued until all the BPA-TA solids were collected. The isolation process was repeated multiple times. The wet cake was transferred to a foil pan and placed in a vacuum oven. The samples were dried at 90-95°C under nitrogen for 16 hours. kg of BPA-TA isomers were collected with a yield of 80.39% for hydrolysis / quenching. ICP-Dig: Sodium (274 ppm), Potassium (2.7 ppm) ), zinc (1.5ppm), calcium (3.2ppm), aluminum (0ppm), Iron (7.7ppm), Titanium (0ppm), Phosphorus (8.3ppm), IC-Total: Sulfur Acid (1,208 ppm), chloride (671 ppm), phosphoric acid (<20 ppm), nitric acid (5 30ppm), nitrite (128ppm), UPLC: 3,3'-BPA-TA (94.8 4mol%), 3,4'-BPA-TA (2.91mol%).
[0116] The vessel was charged with o-DCB (296 kg) and the combined BPA-TA dried cake ( 55.89 kg, 100.4 mol) were charged. Nitrogen was added and the mixture (352 kg , 15wt% solids for BPA-DA) was agitated, and then 182-18 The vessel was heated to 7°C. After 2.5 hours, the vessel reached the target temperature. The solution was then heated for 3 hours. Allow concentration to a total mass of 17 kg (16.5 wt% solids) and, if necessary, This level was maintained by adding fresh o-DCB at 182°C. After 20 hours, Karl Fischer analysis showed that the overhead contained 127 ppm water. UPLC analysis of the reactor bottoms showed 94.6 mol% BPA-DA isomers. The temperature of the vessel was then adjusted to 100°C and left overnight for agitation. It was blocked.
[0117] DI water (95.4 kg) in the hold tank, then sodium bicarbonate (0.963 kg). Then, add 8 aq.NaHCO3 to make a 1.0wt% NaHCO3 aqueous solution. The contents of the acid dianhydride solution were cooled to 85-90°C while being heated to 5-90°C. A portion of the aq. bicarbonate solution (64.2 kg) was transferred to a ring-closing vessel and heated to 80-90°C. The temperature was maintained at 0° C. At this point, the two-phase mixture weighed 400 kg. The contents were stirred for 10 minutes. Mix with 90-100% agitation throughout, which will reach a pressure of 1.4 psig. A sample was taken and the upper (aqueous) layer was found to have a pH of 8. Afterwards, agitation was stopped and the layers were allowed to separate for 2 hours. The bottom layer, containing the BPA-DA isomers in CB, was then transferred to a second vessel and the ring-closing vessel The temperature was maintained at 85-90°C with agitation until the cell level reached 62 kg. The remaining upper aqueous layer was then drained to waste. The total contents of the second vessel were 3 The aq. NaHCO3 was drained from the holding tank and It was then rinsed and cleaned with DI water. Water (300 kg) was charged and heated to 85-90°C. The contents were transferred again to the first vessel with agitation and heating to 85-90°C. Next, DI water (125 kg) was transferred from the holding tank to the first vessel and cooled to 442 The total vessel weight was given in kg. The mixture was heated at 90-100% power for 10-15 min. After this, the agitation was stopped. After this, the mass in the first vessel (the clear, colorless aq. layer) The yellow lower (organic) layer was again transferred to a second vessel until the weight was reduced to 125 kg. The mass in the first vessel was observed to be 342 kg. The aq. wash solution was measured to have a pH value of 4-5 and was discarded in an appropriate waste disposal container. At the same time, the contents of the second vessel were maintained at 85-90°C with agitation. When the first vessel is empty, the material in the second vessel is replaced with fresh o-DCB (40k Transfer again to the first vessel using the washing solution from step g) and heat to 85-90°C with agitation. Maintained.
[0118] DI water (107 kg) was transferred from the holding tank to the mixture, and then 90-100 The mixture was agitated at 10% output for 10-15 minutes. The mixture was allowed to separate for 60 minutes. The yellow (organic) phase was then allowed to separate until the emulsion layer was reached. The layer was again transferred to a second vessel. UPLC analysis of the bottom (organic) layer revealed 3,3'-BPA- It showed the presence of AnhDA (14.18 mol%) but not 3,3'-BPA-TA. The emulsion was isolated (8 kg) and separated in the laboratory, and the bottom layer (4 kg) was retained. The upper aqueous layer (109 kg) in the first vessel was poured into a waste tote equipped with a bag filter. The filter collected 19.94 kg of wet cake, which was approximately 3, It was observed that the 3'-BPA-TA was the main component of the 3'-BPA-TA. The contents of the second vessel, together with the collected solids and the organic layer separated from the emulsion, are The contents were then transferred again to the empty first vessel. Heating to 85°C eliminated water and ring-closed any BPA-TA present. The vessel was also rinsed with additional o-DCB (40 kg), which was then transferred to the first vessel. The contents were heated until the overhead indicated <30 ppm water present. At this point, the bread solids test showed a content of 16.4 abs.wt.%. The solids present (31.65 kg of BPA-DA isomers) were shown.
[0119] A large amount of solid matter was found remaining in the second vessel. The internal mass reached 400 kg. The vessel was charged with o-DCB until the mixture was dissolved. The vessel was heated to 180°C and the remaining After several hours, the contents were cooled to 150° C. and the mixture was cooled to 150° C. I kept it on over the weekend. Then I put the water overhead in the car with 107.4 ppm. The contents were reheated to 182-185°C until shown by L. Fisher analysis. C confirmed that all BPA-TA had been ring-closed to BPA-DA. The contents were transferred to a first vessel maintained at 185° C. and concentrated to 298 kg, then The vessel samples were cooled to 170°C and held overnight. (93.7 mol%) and BPA-AnhDA (4.45 mol%). The formulation was run at a concentration of 15.1 for an expected yield of 86.1% from BPA-TA. It was determined that the solid content was 1 wt% (45.03 kg of BPA-DA out of the expected 52.27 kg). ICP-Dig: Sodium (15 ppm), Potassium (12 ppm), Zinc ( 4.7ppm), calcium (7.8ppm), aluminum (1.8ppm), iron (1 8ppm), titanium (0ppm), phosphorus (22ppm), IC-extract: chloride (3.01 ppm), sulfate (14.65 ppm), phosphoric acid (1.3 ppm), nitric acid (<0.5 ppm ), nitrite (<0.5ppm).
[0120] The BPA-DA solution in o-DCB was then cooled to 160° C. while the second beaker was cooled. The cell was cleaned with o-DCB and drained. Then, the dianhydride solution was added. The 2 micrometer Mott filter is then sent to a second vessel to remove any residuals present. The residual species were removed. The first vessel was then cleaned with water and drained. The filtrate in the second vessel was maintained at 170°C with agitation overnight. The filtrate was then sent back to the first vessel, followed by washing with fresh o-DCB (40 kg). The dianhydride solution was concentrated to 300 kg and then heated to 180-185°C. Solids testing yielded 14.53 wt. % for an estimated yield of 83.4% from BPA-TA. % solids (43.58 kg BPA-DA out of 52.27 kg expected). After: ICP-Dig: Sodium (12.0 ppm), Potassium (10 ppm), Zinc ( 3.7ppm), calcium (1.7ppm), aluminum (4.7ppm), iron (1 9ppm), titanium (0ppm), phosphorus (23ppm), IC-extraction: sulfuric acid (2.74ppm) pm), chloride (45.8 ppm), phosphate (<0.5 ppm), nitrate (<0.5 ppm ), nitrite (<0.5 ppm), UPLC: 3,3'-BPA-DA (95.22 mol %), 3,4'-BPA-DA (2.34 mol%), 3,3'-BPA-dianhydride ( 0.85 mol%).
[0121] The solution was then concentrated to 231 kg at 185°C, then cooled to 120°C, The BPA-DA solid was then separated into 18.8 wt % solids solution. The anhydride solution was used directly for polymerization trials following the procedure described in Example 2. Poly(ether isomers) were synthesized from 4,4'-DDS using phthalic anhydride as a chain terminator. A mide was prepared. The polymer was extruded to form pellets. GPC: Weight average MW=55 ,567, Mn=25,477, PDI=2.18, Mz / Mw=1.56, ICP-D ig: sodium (1.9 ppm), potassium (6.7 ppm), zinc (6.4 ppm) , Calcium (0ppm), Aluminum (0ppm), Iron (14.3ppm), Titanium (0 ppm), phosphorus (11 ppm), IC-extraction: sulfuric acid (22.2 ppm), chloride (7 .98ppm), phosphate (<0.5ppm), nitrate (<0.5ppm), nitrite (<0. 5 ppm), DSC Tg: 261.4°C.
[0122] The purification methods for Examples 14 and 15 are summarized in Table 6. BPA-DA is prepared in o-DCB by dissolving in water using an aqueous solution of sodium bicarbonate. The dianhydride solution is washed to remove ionic species. Subsequent water washes then remove the residual cations from the organic layer. The residual sodium bicarbonate is removed, which is then followed by filtration. Thorium and sulfuric acid (from the sulfuric acid quench of the tetrahydrofuran) are removed to very low levels. The higher sodium content (after filtration) shown in Example 14 is due to improper cleaning. This was attributed to contamination from the damaged vessel.
[0123] [Table 7]
[0124] <Comparative Example 16> N,N'-Ph-BPA-BI (91.13 mol% N,N'-3,3'- BPA-BI and 5.47 mol% N,N'-3,4'-BPA-BI) (3 Additional DI water (30 kg) was added to the hydrolysis vessel containing 49 kg total mass. The reactor was agitated at 70% power and heated to 90°C with a nitrogen purge. Add 45.79 kg, 572.4 mol, >5.5 equiv. of 0% NaOH in water. The vessel was sealed and the internal pressure was reduced to 130-200 psi. Heat for 2 hours until 135 psig (180°C) is reached. Pressure is increased for an additional 5 hours. Maintain 130-135 psig for the duration, then lower the set temperature to 75-80. The agitation was also reduced to 60% power and the mixture was left to soak for the weekend. The vessel was carefully depressurized to 2 psig and a sample was taken. UPLC Analysis indicated that hydrolysis was complete. The washing vessel was filled with o-DCB (1 30 kg) was charged, agitated, and heated to 75-80°C. The aqueous solution of Na was transferred to a washing vessel and agitated at 50% power for 30 minutes. The layers were then allowed to separate. After 45 min, a solution containing o-DCB and aniline was obtained. The lower layer was drained to waste. The upper layer, containing BPA-TA·4Na in water, was diluted with 75–80 The mixture was left to heat at 100° C. To the empty hydrolysis vessel was added o-DCB (130 kg). The contents and the hydrolysis vessel were then washed and heated to 75-80°C. The DI water (40 kg) used for the cleaning was transferred to the cleaning vessel. Agitate at 75-80°C for 30 minutes and then allow the layers to separate. After standing overnight, the lower layer containing o-DCB and aniline was drained to waste. The upper layer, containing a solution of BPA-TA·4Na in water, remained, which had a total mass of 371 kg. The contents of the wash vessel were then mixed with 70-80 ml of water at 40% agitation power. Maintained at 0° C. DI water (30 kg) was added and the contents were heated to 90° C.
[0125] The quench vessel was charged with DI water (81.7 kg), agitated, and then A 50% aqueous solution of H2SO4 (122.5 kg, 624.5 mol, >6 equiv.) was dissolved in Teflon lamination. The transfer line was connected to a 1000cc drum pump via a PVC flexible hose. It was flushed with water (15.8 kg) and sent to a quench vessel, where it was mixed with 220 kg of Then, prior to quenching, the aq. H2SO4 was diluted to 70%. The temperature was increased to 85-90°C using a dimmer output.
[0126] The aqueous solution of BPA-TA·4Na in the cleaning vessel was kept at 85-90℃ for 45 minutes. The wash vessel was then filled with DI water (60 kg). The mixture is rinsed with ethyl acetate and reheated to 85-90°C, and the rinse is also sent to the quench vessel. After approximately 2 hours and 15 minutes, when the transfer was complete, the agitation power was increased to 100%. After 45 minutes, the milky mixture was agitated at 80% power. The flask was then sealed at 90° C. and the contents were kept overnight to ensure complete protonation of the carboxylic acid species. A sample of the contents was then visually inspected and showed good flow without stickiness. The solids content was The slurry was cooled to 70-80°C after it was quickly precipitated from the aqueous medium.
[0127] Using Teflon lined flexible hoses and fittings of suitable compatible construction materials. The slurry was then loaded onto a 40 liter Nutsche filter containing 60 micrometer Teflon filter media. At 50 psig, the liquid was separated from the solids by a Nutsche filter. After filtration was complete, the product cake was poured into a Nutsch tote. The transfer process was repeated until the bottom section of the filter was filled. Ruta was depressurized.
[0128] The hold tank was filled with DI water, heated to 90°C, and pressurized to 50 psig. The water is then transferred from the holding tank to the Nutsche filter in a slow continuous flow. The product cake was washed. The filtrate was sent to a polypropylene tote as before. The waste stream was monitored until H was obtained and the filtrate showed 70 ppm of sodium ions present. The water flow was then stopped and the filter was pressurized to 50 psig to remove the water. Most of the cake was removed and the wet cake was finally transferred to a plastic drum for a total of 584 gallons. of aqueous wastewater was generated for the first product cake (17.5 kg). The cake was shown to be 88.7 wt% solids.
[0129] The above cake isolation procedure was repeated except that the DI water was introduced into the Nutsche filter at a much faster rate. During the two hour flush, the waste stream contained only 80 ppm of sodium present. After the filtrate was found to contain 40 ppm sodium, The pH value of the solution was measured to be 3.5. The water flow was then stopped and the filter was subjected to 50 psi The mixture was pressurized to 1000 g to remove most of the water, and the wet cake was finally transferred to a plastic drum. A total of 159 gallons of aqueous waste was generated for the second product cake (16.5 kg). A pan solids test showed the cake to be 83.6% solids.
[0130] After the cake is formed, add DI water (at 90°C) to fill the Nutsche filter. The cake isolation procedure above was followed, except that the system was closed and left to soak for 30 minutes. The batch was then allowed to cool and then the water was removed by applying pressure to a Nutsche filter. The protocol was repeated several times. After a total of 4-5 hours of batch flushing, the aqueous filtrate was It contained 40 ppm sodium and a pH value of 3.5. The water flow was then stopped. The filter is then pressurized to 50 psig to remove most of the water, and the wet cake is finally poured into the filter. The third product cake weighing 8.0 kg was transferred to a stick drum for bread solids testing. A total of 42.0 kg of white BPA-TA wet The cake was isolated with an estimated dry weight of 35.49 kg. The product was used directly in the ring closure step without further drying. ICP-Dig: Sodium (81. 5), potassium (5.3ppm), zinc (2.4ppm), calcium (12.3ppm) ), Aluminum (2.4ppm), Iron (2.4ppm), Titanium (0.6ppm), Li IC-Total: Sulfuric acid (694 ppm), Chloride (2,903 ppm) m), phosphate (<20 ppm), nitrate (3,163 ppm), nitrite (383 ppm), UPLC: 3,3'-BPA-TA (92.68%) and 3,4'-BPA-TA (7 .32%).
[0131] Combined BPA-TA wet cake (35.49 kg dry basis, 63.77 mol) and o-DCB (348 kg) were charged into a ring-closing vessel to prepare an 8.7 wt% mixture. Nitrogen was added, the mixture was agitated, and the contents were then heated to 182-187°C. After a few hours, the vessel reached the target temperature. Over the next 80 minutes, the mixture was heated to 255k. The mixture was allowed to concentrate to a total mass of 100 g (13 wt % solids). At this point, all solids were The solution dissolved to form a yellow solution, and the resulting sample was analyzed by Karl Fischer analysis. The reactor weight was maintained and the reactor was cooled for an additional 1 h. After 0 min, the overhead sample showed a Karl Fischer analysis of 132ppm. The vessel temperature was then adjusted to 160°C and incubated overnight. The next morning, the sample was checked for complete cyclization of BPA-DA. Nevertheless, the overhead samples were not found to be soluble in the Karl Fischer analysis. The contents were then adjusted while maintaining the reactor weight until it was determined that the reactor contained 29 ppm water. Drying continued for the next 6 hours. Then the temperature was adjusted to 120°C and agitated overnight. It was blocked off for the purpose.
[0132] The contents are recirculated through a 2 micrometer Mott filter to remove any trace metals present. After a total of 12 hours, the solution was transferred to a preheated (120°C) holding tank. The ring-closing vessel was cleaned with additional o-DCB (10 kg). This was also sent to the holding tank from the Mott filter. A sample of 275 kg of filtrate was taken. indicated that it was 10.3 wt% solids.
[0133] The crystallization vessel was thoroughly cleaned with fresh o-DCB, drained, and then The flex hose was then connected to the Nutsche filter from the holding tank outlet. A second flex hose was connected from the Nutsche filter outlet to the inlet of the crystallization vessel. The flex hose and Nutsche filter were then connected to the inlet prior to transfer. The filtrate in the holding tank was then pressurized and heated to 90-140°C. From the filter, the mixture was sent to the crystallization vessel. Additional o-DCB (40–50 kg) was used to The rinse tank was then rinsed and the Nutsche filter was also passed through the crystallization vessel.
[0134] After transfer, the final filtrate (305.5 kg) was agitated and heated to 170°C. After 10 minutes, a sample was taken and found to contain 8.06 wt% solids, approximately The solution then had 24.62 kg (74.2% yield) of product present. Heat to 5-187°C and concentrate to 140 kg (17.6 wt% solids) over the next 2 hours. Heating was discontinued and the solution was allowed to cool overnight with agitation. The cell temperature reached 78°C. Heptane (40 kg) was then inerted with nitrogen. The mixture was then charged into a crystallization vessel and agitated for 10 minutes. This was repeated 10 times (total of 120 kg heptane). Once the addition was complete, the crystallization vessel was The hot oil in the cell was closed to further cool the reactor and promote crystallization of the product.
[0135] After agitating the slurry for 2 days, the temperature reached 53°C. The Nutsche filter was removed and visually observed for lack of stickiness and good flow properties. Clean with CB (5gal), dry and then apply 60 micrometer Nomex A filter medium was then installed. The slurry was then poured into the hose using a Teflon-lined flexible hose. The first cake was transferred to a Nutsche filter by light nitrogen pressure and filtered as previously described. After the Nutsche filter was heated to remove the solvent, fresh heptane was added to the cake. The heptane wash was then removed under pressure. This was then repeated once more. Remove as much of the heptane wash as possible before drying. A total of three product cakes were made in this manner, with care taken to separate the wet cake from the aluminum. Place in a foil pan and heat in a vacuum oven at 140°C until a consistent mass is obtained. (30 in. Hg). A total of 22.5 kg (67.8% yield) of BPA-D The A isomer was obtained as an off-white solid. YI value: 21.1 (L=91.87, a=-2. 72, b=12.20), DSC (融点) = 188.0 °C, UPLC: 3,3'-BPA -DA(96.50%), 3,4'-BPA-DA(0.64%), 3,3'-BPA- Diacid anhydride (2.42%), ICP-Dig: Sodium (0.9 ppm), Potassium ( 4.3ppm), zinc (3.3ppm), calcium (10.5ppm), aluminum (0.4ppm), iron (33.2ppm), titanium (0ppm), phosphorus (5.3ppm) , IC-extraction: Sulfate (14ppm), Chloride (84.4ppm), Phosphate (<0.5ppm) m), nitrate (<0.5 ppm), nitrite (<0.5 ppm).
[0136] The purification methods used in Example 6 and Comparative Example 16 are summarized in Table 7. BPA-TA·4Na salt The BPA-TA intermediates prepared from either nitric acid or sulfuric acid quenching of The homogeneous solution is then subjected to Mott filtration (2 micrometer filter), then o-DCB alone (Example 6) or heptane / In this manner, sodium nitrate, nitric acid, and zinc were added to the solution. Nitric acid, sulfuric acid, and chlorides are removed to very low levels.
[0137] [Table 8]
[0138] <Comparative Example 17> The following procedure used 3,3'-BPA-TA with the following profile: UPLC: BPoTA isomers (95.93%), ICP-Dig: sodium (37.1 ppm), Potassium (13.9 ppm), zinc (4.9 ppm), calcium (17.3 ppm), Aluminum (2.1ppm), Iron (16.6ppm), Titanium (<0.5ppm), Li IC-Total: Sulfuric acid (176 ppm), Chloride (1,240 ppm) m), phosphate (<20 ppm).
[0139] With overhead stirrer, Dean-Stark trap, and condenser In a 500 mL two-neck round-bottom flask, add ground 3,3'-BPA-TA (20.0 g, 3 5.9 mmol, 1 equiv.), o-DCB (200 g, 154 mL), and sulfuric acid (0.0 The mixture was placed under nitrogen. The mixture was heated to 150°C and placed in a 69°C oil bath and agitated at 150 rpm. After heating for approximately 1 hour and 45 minutes, the distillate of o-DCB / H2O (7.34 g) was trapped. Additional o-DCB (52.3 g) was added to rinse the walls of the flask. After an additional 25 min, the reaction was allowed to cool to room temperature overnight. The next morning, the mixture was diluted with 180 The mixture was then reheated to 150°C with rpm agitation. After approximately 90 minutes, UPLC analysis showed that the reaction This indicates that the response is complete.
[0140] The solution was then cooled to 70° C. and heptane (200 mL) was charged. The mixture was stirred for 20 minutes and then the slurry was poured into a medium fritted glass funnel. Filter, rinse with heptane (~100 mL), and place in a vacuum oven at 96 °C. After drying by hexane, 12.48 g of the dianhydride was obtained as an off-white to tan solid in 66.7% yield. UPLC: BPA-DA isomers + BPA-AnhDA (97.31%), ICP-Dig: Sodium (26.8), Potassium (17.8 ppm), Zinc (2.8 ppm), calcium (13.1 ppm), aluminum (6.9 ppm), iron (13. 9ppm), titanium (<0.5ppm), phosphorus (3.3ppm), IC-extraction: sulfuric acid (8 82ppm), chloride (2.5ppm), and phosphate (<0.5ppm).
[0141] The purification methods of Example 14 and Comparative Example 17 are summarized in Table 8. BPA in o-DCB To prepare -DA, the BPA-TA intermediate was ring-closed with aq. NaHCO3. When washing the solution and Mott filtration failed to give pure material ( In Example 14, the additional process of crystallization from o-DCB was successful. When the BPA-TA ring closure to form was catalyzed by sulfuric acid (Comparative Example 17), Crystallization of the dianhydride from butane / o-DCB removes sulfuric acid to acceptable levels. But it failed.
[0142] [Table 9]
[0143] <Example 18> Solution of 3,3'-BPA-DA in o-DCB (118.21 g, 21.75 wt%) (70 ppm sodium, 58.55 ppm chloride, and 154.46 ppm sulfuric acid Celite (10.05 g) was added and mixed. The mixture was heated to 100°C with agitation for 30 minutes. The filtrate was filtered hot through a 4-5.5 μm sintered glass funnel. The solids content was determined to be 20.85 abs.wt% by ICP-Dig : Sodium (0), Potassium (10.3ppm), Zinc (8.8ppm), Calcium (8.1ppm), aluminum (2.3ppm), iron (2.2ppm), titanium (1. 8ppm), phosphorus (11ppm), IC-extraction: sulfate (0.76ppm), chloride (<0 .5ppm), Phosphate (<0.5ppm), Nitrate (<0.5ppm), Nitrite (<0.5 ppm).
[0144] <Comparative Example 19> The following comparative example used the 3,3'-BPA-DA solution prepared in Example 7. '-BPA-DA solution (56.63 g, 22.20 wt% solids, 12.57 g dry weight ) into a 100 mL round-bottom flask with a magnetic stir bar and Celite (9.3 g). The mixture was stirred at 90°C for 5 min and then transferred to a medium frit (10-1 The celite was filtered through a 6 micrometer glass funnel with room temperature o-DCB (25 ml The combined filtrate was concentrated to give 12.54 g (99.8% yield). ICP-Dig: Sodium (84.5), Potassium (8.2pp m), zinc (2 ppm), calcium (13.5 ppm), aluminum (1.7 ppm ), iron (3.1ppm), titanium (<0.5ppm), phosphorus (6.6ppm), IC-extraction Output: Sulfuric acid (178.4 ppm), chloride (5.3 ppm), phosphoric acid (<0.5 ppm), Nitrate (<0.5ppm), Nitrite (<0.5ppm).
[0145] The purification methods of Example 18 and Comparative Example 19 are summarized in Table 9. BPA in o-DCB The prepared solution of -DA is treated with an adsorbent and heated to remove contaminants. As shown in Example 18, BPA-TA is initially at a fairly low ppm. Sodium, chloride, nitrate, nitrite, and sulfuric acid is removed to a level below 1 ppm. As shown in Comparative Example 19 Celite removes most of the ionic contaminants, but very high levels of BPA remain. When present in -TA, additional purification methods may be required.
[0146] [Table 10]
[0147] <Example 20> The following procedure used 3,3'-BPA-DA with the following profile: ICP-D ig: Sodium (4), Potassium (13 ppm), Zinc (5 ppm), Calcium (7 ppm), Aluminum (0ppm), Iron (0ppm), Titanium (0ppm), Phosphorus (6 ppm), IC-extraction: Sulfate (1.4 ppm), Chloride (1.2 ppm), Phosphate (<0 .5ppm), Nitrate (0.9ppm), Nitrite (<0.5ppm), UPLC: 100% Pure desired material (BPA-DA isomers + BPA-AnhDA). Mechanical stirrer Place a 500 mL round-bottom flask under nitrogen with a Dean-Stark trap, and a condenser. To Lasco, solid 3,3'-BPA-DA (26.414 g, 50.75 mmol, 0. 9685 equivalents), DDS (13.01g, 52.40mmol, 1.00 equivalents), PA( 0.660 g, 4.46 mmol, 0.0850 equiv.), and o-DCB (151 g, 116 mL) was added all at once. The reaction flask was then placed in a 150° C. oil bath. The nitrogen flow was increased with agitation at 90-100 rpm. The temperature was adjusted to 182-185°C to concentrate the reaction.
[0148] (For example, when the prepolymer becomes a heterogeneous mass) It was observed that the glue ball stage was reached after the ball stage. Agitation was then increased to 250 rpm. After 30 minutes at 182-185°C After 1 h total cycle time, the reaction became a homogenous orange solution. The distillate of B (66 g) was drained from the trap. At this point, the reactor contents were 30 wt. The nitrogen flow was reduced, the heat tape was turned off, and the polymerization was continued for 182 h. The mixture was stirred overnight at 185° C. After a total cycle time of 16 hours, the mixture was cooled to 185° C. and then cooled to 185° C. for 24 hours. The poly(etherimide) solution was then poured into a pan and cooled. GPC: Weight average MW= 45,860, Mn=19,495, PDI=2.35, Mz / Mw=1.60, ICP -Dig: Sodium (14.8), Potassium (13.9 ppm), Zinc (8.8 ppm ), calcium (27.8ppm), aluminum (17.9ppm), iron (7ppm) , titanium (0.6ppm), phosphorus (21.1ppm), IC-extraction: sulfuric acid (5.3ppm ), chloride (5.10ppm), phosphate (<0.5ppm), nitrate (<0.5ppm), Nitrous acid (<0.5 ppm), DSC-Tg: 266°C.
[0149] <Example 21> The BPA-DA isomers prepared in Example 2 were used in the following process. ICP-Dig: Sodium (2ppm), Potassium (5ppm), Zinc (0ppm), Calcium (0ppm) pm), aluminum (0 ppm), iron (0 ppm), titanium (0 ppm), phosphorus (12 ppm), IC-extraction: Sulfate (10.06 ppm), Chloride (<0.5 ppm), Phosphate (<0.5ppm), nitric acid (<0.5ppm), nitrite (<0.5ppm). o-DCB (132 kg) and the BPA-DA isomer prepared above (43.73 kg dry The contents were heated to 105°C with agitation. Heat was added and then phthalic anhydride (510 g, 3.44 mol) was added. The contents were then flushed with nitrogen. The vessel was then charged with m-PD (9.309 kg, 86.08 mol). The internal temperature was raised to 130°C. After 1 hour, the internal temperature was adjusted to 180°C. After an additional 2 hours, samples were taken for stoichiometric analysis. The solution was then kept at 180° C. for 1 hour, correcting as necessary until 1.5% excess dianhydride was obtained. While maintaining the temperature, the material was passed through a Mott filter (2 micrometers) into a second vessel. The solution was concentrated to 35 wt% solids and then kept at 140°C overnight. The polymer solution was extruded to produce pellets. GPC: Weight average MW=52,692, Mn=1 5,750, PDI=3.35, Mz / Mw=1.51, ICP-Dig: Sodium ( 8), Potassium (10ppm), Zinc (0ppm), Calcium (3ppm), Aluminum Aluminum (0ppm), Iron (0ppm), Titanium (0ppm), Phosphorus (8ppm), IC-extraction Output: Sulfuric acid (2.9ppm), chloride (0.9ppm), phosphoric acid (<0.5ppm), nitric acid (<0.5ppm), nitrite (<0.5ppm), DSC-Tg: 268.7℃.
[0150] <Comparative Example 22> The following procedure used 3,3'-BPA-TA with the following profile: ICP-D ig: sodium (269ppm), potassium (5.6ppm), zinc (3.1ppm) , Calcium (5.4ppm), Aluminum (0ppm), Iron (0ppm), Titanium ( 0ppm), Phosphorus (5.5ppm), IC-Total: Sulfate (1,082ppm), Chloride (4,017ppm), phosphoric acid (<20ppm). Mechanical stirrer, Dean In a 250 mL round bottom flask under nitrogen with a Stark trap and condenser, add The compound 3,3'-BPA-TA (23.25 g, 41.78 mmol) and o-DCB (1 The contents were stirred at 200 rpm in an oil bath set at 200°C. After 1 hour, 39.5 g of distillate was drained from the trap and heated under a nitrogen stream. After an additional hour, o-DCB (15 mL) was added to obtain a homogenous yellow mixture. Added the color solution and allowed it to cool to room temperature overnight.
[0151] Then, 4,4'-DDS (10.66 g, 42.9 mmol), PA (0.343 g, 2.32 mmol), and o-DCB (20 mL), and the flask was heated to 200°C. The polymerization solution was heated again to 28°C. The nitrogen flow was increased with agitation at 200 rpm. After heating for 10 minutes, it was observed that the ball stage was reached at 175-185°C. During this time, the agitation was reduced to 120 rpm. After the ball stage, Agitation of the homogeneous yellow solution was increased to 200 rpm. After an additional 38 minutes, the oil The bath temperature reached 196°C and the distillate of H2O / o-DCB (74.3 g) was drained from the trap. At this point, the reactor contents were estimated to be 35 wt% solids. After a total of 5.5 hours, a sample was taken for stoichiometry. Additional 3,3'-BPA-DA (370 mg) was added along with o-DCB (5 mL). The contents were allowed to concentrate again to 35 wt% solids. The following morning, a second run for stoichiometry was performed. A sample of 2 was taken and additional 3,3'-BPA-DA (211 mg) and o-DCB ( 5 mL) was added to the flask. After a total polymerization time of 28 hours, poly(etherimide) The solution was poured into a pan and cooled. The sample was devolatilized at 385°C for 20 minutes. C: Weight average MW=21,238, Mn=10,118, PDI=2.10, Mz / Mw =1.41, ICP-Dig: Sodium (200), Potassium (12.1 ppm), Nitrogen Lead (16.2ppm), calcium (36.4ppm), aluminum (5.2ppm) , iron (13.2ppm), titanium (1.5ppm), phosphorus (10.3ppm), IC-extraction Output: Sulfuric acid (440.7ppm), chloride (13.6ppm), phosphoric acid (<0.5ppm) , nitric acid (<0.5 ppm), nitrous acid (<0.5 ppm), DSC-Tg: 256.9℃.
[0152] Table 10 shows that when highly pure BPA-DA is used as the monomer, highly pure poly(ethylene glycol) It has been shown that poly(etherimides) can be prepared in o-DCB (Example 5 , 20, and 21). However, highly contaminated BPA-DA was used. When the reaction was continued (Comparative Example 22), the resulting poly(etherimide) had high levels of It will also have inorganic contaminants and lower thermal properties (Tg).
[0153] [Table 11]
[0154] <Comparative Example 23> With overhead stirrer, Dean-Stark trap, and condenser In a 3-neck 250 mL round-bottom flask, add N-phenyl-3,3'-BPA-BI (C 43 H3 0N2O6) / N-phenyl-3,4'-BPA-BI(C 43 H 30 N2O6)(96 .5:3.5 ratio, 10.00 g, 14.91 mmol), 4N aq. NaOH (14. The reaction mixture was placed in an oil bath at 105 °C. After 7 hours, the sample showed that all starting material had been consumed and N-phenyl- 3,3'-BPA-TAMA·3Na (2.98%) and N-phenyl-BPA-DA The mixture of DA·2Na (97.02%) was present. After 17 hours, UPLC analysis showed that all starting material was consumed and N-phenyl-3,3'-BPA-TAM A 3Na (14.25%) and N-phenyl-BPA-DADA 2Na (85.7%) Water (10 mL) was drained from the trap, indicating the presence of a 5% mixture. Then, o-DCB (70 mL) was added to the reaction flask.
[0155] The temperature of the reaction mixture was increased to 115°C, which was followed by the addition of 50% aqueous H2SO4 (1 7.55 g, 89.46 mmol) was added dropwise. After the addition was complete, The temperature was further increased to 125° C. and stirring was continued for 3 hours. The heat was removed and stirring was continued for 3 hours. The mixture was stopped and the layers separated within a few minutes. The upper aqueous layer was discarded and fresh DI water (100 mL) was added. The mixture was stirred for 1 minute and then the layers were allowed to separate. The upper aqueous layer was removed. The water washing procedure was repeated several more times until the aqueous layer had a pH of 4. The organic layer was sampled and analyzed by UPLC to determine the 3,3'-BPA- DA (14.7%), N-phenyl-3,3'-BPA-anhydride imide (76.2%), and N-phenyl-3,3'-BPA-BI (7.5%). ICP digestion of this sample after stripping and washing with water revealed 19 ppm Na, < 5.0ppm K, <1.0ppm Zn, 3.6ppm Ca, 6ppm Al, <1 0 ppm Fe, <1.0 ppm Ti, and <10 ppm P.
[0156] Additional o-DCB (100 mL) was added to the flask and the mixture began to heat to 185 °C. After 1 hour, the temperature reached 180°C. The Stark trap was drained with a water / o-DCB (30 mL / 42 mL) azeotrope. Most of the solids had dissolved into a light yellow solution. After an additional hour of heating, the flask was cooled to room temperature. The mixture was then allowed to cool to room temperature. Filtration through fiber filter paper gave a light yellow filtrate. UPLC analysis of the filtrate revealed 3,3' -BPA-DA (15.6%), N-phenyl-3,3'-BPA-anhydride imide (75 0.5%) and N-phenyl-3,3'-BPA-BI (7.3%). ICP digestion of this sample after removal of the solvent showed significant improvement of inorganic impurities. In other words, after filtering and reanalyzing it, the filtering step was not performed. It was found that further reducing the amount of any impurities did not result in a significant reduction in the amount of any impurities. ppm Na, <5.0 ppm K, 16.7 ppm Zn, 3.3 ppm Ca, 4. 5ppm Al, 1.9ppm Fe, <1.0ppm Ti, and <10ppm P It contained.
[0157] The present disclosure further encompasses the following aspects.
[0158] Aspect 1: Formula [ka] Bisphenol A dianhydride [wherein R a and R b are each independently halogen or is monovalent C 1-6 is an alkyl group, and p and q are each independently an integer from 0 to 4; , preferably, p and q are each 0], and a sodium ion, a potassium ion, ions, calcium ions, zinc ions, aluminum ions, titanium ions, iron ions , phosphorus ion, phosphate ion, sulfate ion, chloride ion, nitrate ion, and nitrite ion and at least one of the following: The method includes contacting a bisphenol A dianhydride composition with a halogenated solvent to dissolve the bisphenol A dianhydride composition. forming a liquid, filtering the solution to remove ionic species, and filtering the solution with an aqueous medium; The ionic species are removed by washing, and the bisphenol A dianhydride is crystallized from the solution to form an isomer. one by removing ionic species and the other by contacting the solution with an adsorbent to remove ionic species. The above and more.
[0159] Embodiment 2: The method of embodiment 1, wherein the method comprises filtering the solution, and filtering , the solution is equal to or less than 2 micrometers, preferably 0 This involves passing the sample through a filter having a pore size of 0.2 to 0.45 micrometers.
[0160]
[0023] Aspect 3. The method of aspect 1 or 2, further comprising washing the solution with an aqueous medium and The system medium is an aqueous caustic alkali solution, preferably an aqueous sodium bicarbonate solution, more preferably an aqueous sodium bicarbonate solution. The aqueous sodium bicarbonate solution has a concentration of 10 to 10 weight percent sodium bicarbonate. and optionally thereafter washing the solution with water.
[0161] Embodiment 4: The method of any one or more of embodiments 1 to 3, wherein the method comprises: The method includes crystallizing the dianhydride from the solution, and crystallizing bisphenol A dianhydride. Optionally, an anti-solvent is added to the solution and cooled to an effective temperature to provide a slurry. This includes:
[0162] Embodiment 5: The method of embodiment 4, wherein the anti-solvent is a non-polar solvent, preferably the anti-solvent is heptagonal. ethane, hexane, pentane, benzene, ligroin, or combinations thereof; More preferably, the anti-solvent comprises heptane.
[0163]
[0023] Embodiment 6: The method of any one or more of embodiments 1 to 5, wherein the method comprises contacting the solution with an adsorbent. The method includes the steps of: subjecting the adsorbent to a treatment with a sorbent selected from the group consisting of celite, diatomaceous earth, silica, alumina, and combinations thereof; The method further comprises: or filtering through a filter having a pore size of 4 to 5.5 micrometers. nothing.
[0164]
[0023] Aspect 7. The method of any one or more of aspects 1 to 6, wherein the halogenated solvent is an ortho -Dichlorobenzene, para-dichlorobenzene, meta-dichlorobenzene, trichlorobenzene or any combination thereof.
[0165]
[0023] Aspect 8. The method of any one or more of aspects 1 to 7, wherein the divalent bisphenol A group The bond is at the 3,3', 3,4', or 4,4' positions, preferably at the 3,3' positions. do.
[0166]
[0023] Aspect 9. The method of any one or more of aspects 1 to 8, comprising: The compound is an isomer mixture, and preferably contains 10 to 100% by weight of bisphenol A dianhydride. Percentage of bisphenol A dianhydride divalent bonds of bisphenol A groups at 3,3' position More preferably, 90 to 100 weight percent of bisphenol A dianhydride is It has divalent bonds of bisphenol A groups of bisphenolic dianhydride at the 3,3' positions.
[0167] Aspect 10: Bisphenol A dianhydride made by the method of any of aspects 1 to 9. The purified bisphenol A dianhydride contains less than 25 ppm each of sodium ion, potassium ion, calcium ion, zinc ion, aluminum ion, titanium ion ions, iron ions, and phosphorus ions, as well as less than 50 ppm each of phosphate ions, sulfate ions ions, chloride ions, nitrate ions, and nitrite ions.
[0168]
[0036] Aspect 11. The method of any one or more of aspects 1 to 9, comprising: The aqueous composition is formed by hydrolyzing bisphenol A bisimide to the corresponding bisphenol A tetraimide. and contacting the bisphenol A tetraacid salt with a mineral acid to form the corresponding bisphenol A tetraacid salt. and reacting bisphenol A tetraacid with a halogenated solvent to form bisphenol A tetraacid. forming a mixture and heating the mixture to an effective temperature to form the corresponding bisphenol A; forming bisphenol A dianhydride from bisphenol A tetraacid, optionally in the presence of a mineral acid; and isolating bisphenol A dianhydride from the reaction mixture. The method comprises the steps of: This is done in the absence of
[0169] Aspect 12: A purified bisphenol made by the method of any of aspects 1 to 9. A poly(ether) compound having repeating units derived from the polymerization of an A dianhydride composition and an organic diamine. Poly(ether imide)s each containing less than 25 ppm sodium ion , potassium ion, calcium ion, zinc ion, aluminum ion, titanium ion , iron ions, and phosphorus ions, as well as less than 25 ppm each of phosphate ions and sulfate ions , chloride ions, nitrate ions, and nitrite ions.
[0170] Embodiment 13: The poly(etherimide) of embodiment 12, wherein the organic diamine is 4,4′- Diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 3,3'-dia Diphenyl sulfone, meta-phenylenediamine, para-phenylenediamine, ol tri-phenylenediamine, or a combination thereof.
[0171]
[0036] A method for producing an article of manufacture comprising the poly(etherimide) of any one of claims 12 to 14. Preferably, the article of manufacture is an optical component, more preferably a lens.
[0172] Aspect 15: Formula [ka] Bisphenol A tetraacid [wherein R a and R b are each independently a halogen or a monovalent C 1-6 alkyl group, and p and q are each independently an integer of 0 to 4. or, in the formula, p and q are each 0], and sodium ions and sulfate ions and at least one of: The method comprises washing the bisphenol A tetraacid composition with water at a temperature of 85 to 95 degrees. and optionally agitating the composition during washing. and collecting the bisphenol A tetraacid composition, preferably by centrifugation. The phenol A tetraacid composition contains less than 100 ppm each, preferably less than 80 ppm each, more preferably Generally, sodium ions, potassium ions, calcium ions, etc., are between 0.1 and 75 ppm. and less than 900 ppm, preferably less than 450 ppm, more preferably 0.1 to 4 Contains 25 ppm of sulfate, phosphate, nitrate, and nitrite ions.
[0173] Alternatively, the compositions, methods, and articles of manufacture may comprise any of the methods disclosed herein. may include or consist of any suitable material, step or component; Additionally or alternatively, the compositions, methods, and articles of manufacture may comprise The ingredients of the compositions, methods, and articles of manufacture that are not otherwise necessary to the function or accomplishment of the purpose. Devoid of or substantially free of any material (or species), step, or component It can be formulated as follows:
[0174] All ranges disclosed herein include endpoints, and the endpoints Independently and combinable with each other (e.g., up to 25 wt.%, or more specifically The range of "5wt.% to 20wt.%" is "5wt.% to 25wt.%" (including endpoints and all intermediate values). "Combination" is a blend, The terms "first," "second," and the like include compounds, alloys, reaction products, and the like. does not imply any order, quantity, or importance, but rather distinguishes one element from another. Unless otherwise indicated in this specification or clearly from the context, Unless otherwise stated, the terms "a," "an," and "the" do not denote a limitation of quantity, It should be construed to cover both the singular and the plural. "Or" is otherwise clear. Unless otherwise stated, "and / or" means "and / or." The terms "embodiment," "an embodiment," and the like refer to specific elements described in connection with the embodiment. is included in at least one embodiment described herein and may be present in other embodiments. As used herein, the term "and" means that "Combinations of these" includes one or more of the listed elements and is open-ended and not intended to be limiting. In addition, the elements described may be of various types. It will be understood that the embodiments may be combined in any suitable manner. It is.
[0175] Unless otherwise specified herein, all test standards are current as of the filing date of this application or Where priority is claimed, the test standard shall take effect as of the filing date of the earliest priority application in which the test standard is published. It is the most recent standard.
[0176] Unless otherwise defined, technical and scientific terms used herein are defined as All cited patents have the same meaning as commonly understood by one of ordinary skill in the art to which the application pertains. All patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in this application contradicts or conflicts with a term in an incorporated reference, this application shall govern. Terms from the application take precedence over any conflicting terms in the incorporated references.
[0177] Compounds are described using standard nomenclature. For example, any indicated groups Any position not substituted by A dash that is not between two letters or symbols is understood to have its valences filled. ("-") is used to indicate the point of attachment of a substituent. For example, -CHO is It is attached through the carbon of the carbonyl group.
[0178] As used herein, the term "hydrocarbyl" means, by itself or in combination with another term, Whether used as a prefix, suffix, or fragment, carbon and hydrogen The residue may be aliphatic or aromatic, straight-chain, cyclic, bicyclic, branched, It can be aliphatic, aromatic, linear, cyclic, bicyclic, branched, or unsaturated. It may also contain a combination of saturated and unsaturated hydrocarbon moieties. When a locarbyl moiety is described as substituted, it is understood that it is optionally substituted at a carbon atom of the substituent moiety. and may contain heteroatoms in addition to the hydrogen members. When present, the hydrocarbyl residue may comprise one or more carbonyl, amino, hydroxyl, It may also contain silyl groups, or the like, or it may be a backbone of the hydrocarbyl residue. The term "alkyl" refers to a branched or straight chain unsaturated fatty acid. Aliphatic hydrocarbon groups, such as methyl, ethyl, n-propyl, i-propyl, n-butyl, s -butyl, t-butyl, n-pentyl, s-pentyl, and n- and s-hexyl "Alkenyl" means a straight-chain or means a branched monovalent hydrocarbon radical (e.g., ethenyl (-HC=CH2)). "Koxy" refers to an alkyl group linked through an oxygen (i.e., alkyl-O-), e.g. For example, methoxy, ethoxy, and sec-butyloxy groups. "Alkylene" means means a straight-chain or branched, saturated, divalent aliphatic hydrocarbon radical (e.g., methylene (-CH 2-) or propylene (-(CH2)3-)). "Cycloalkylene" is a divalent cyclic alkylene. Xylene group-C n H 2n-x wherein x is replaced by cyclization(s). "Cycloalkenyl" refers to a group consisting of one or more rings and one or more carbon atoms on the ring. means a monovalent group having a carbon-carbon double bond and all ring members are carbon (e.g., cyclo pentyl and cyclohexyl). "Aryl" refers to any group containing a specified number of carbon atoms. means an aromatic hydrocarbon radical, for example phenyl, tropone, indanyl, or naphthyl "Arylene" means a divalent aryl group. "Alkylarylene" means an alkyl group. "Arylalkylene" refers to an aryl group (e.g., The prefix "halo" refers to a fluoro group. , chloro, bromo, or iodo substituents. A combination of different halo groups (e.g., bromo and fluoro) or only chloro groups are present. The prefix "hetero" means that the compound or group has at least one ring that is a heteroatom. "includes one, two, or three heteroatoms" and each heteroatom or heteroatoms independently represent N, O, S, Si, or P. "Substituted" means that a compound or group has at least one (e.g., 1, 2, 3, or means that the group is substituted by four (4) substituents. Instead of hydrogen, C 1-9 Alkoxy, C 1-9 Haloalkoxy, nitro(-NO2 ), cyano (-CN), C 1-6 Alkylsulfonyl (-S(=O)2-alkyl), C 6-12 Arylsulfonyl (-S(=O)2-aryl), thiol (-SH), thio Cyano (-SCN), Tosyl (CH3C6H4SO2-), C 3-12 Cycloalkyl, C 2-12 Alkenyl, C 5-12 Cycloalkenyl, C 6-12 Aryl, C 7-13 Aryl alkylene, C 4-12 Heterocycloalkyl, and C 3-12 Hetero Ally However, the normal valence of the atom being substituted is not exceeded. The number of carbon atoms listed excludes any substituents. For example, -CH2CH2CN is It is a C2 alkyl group substituted by a nitrile.
[0179] While specific embodiments have been described, alternatives, modifications, and variations that are not presently foreseen or possible may be made. Variations, improvements, and substantial equivalents may occur to the applicant, or others skilled in the art. Therefore, the appended claims as filed and as they may be amended are consistent with all of the above. It is intended to cover all such alternatives, modifications, variations, improvements, and substantial equivalents.
Claims
1. formula 【Chemistry 1】 Bisphenol A dianhydride, a and R b are each independently halogen or is monovalent C 1-6 is an alkyl group, and p and q are each independently an integer from 0 to 4; , preferably, p and q are each 0], and a sodium ion, a potassium ion, ions, calcium ions, zinc ions, aluminum ions, titanium ions, iron ions , phosphorus ion, phosphate ion, sulfate ion, chloride ion, nitrate ion, and nitrite ion and at least one of the following: And, The method further comprising: The bisphenol A dianhydride composition is contacted with a halogenated solvent to form a solution. Steps and filtering the solution to remove ionic species; washing the solution with an aqueous medium to remove ionic species; crystallizing bisphenol A dianhydride from said solution to remove ionic species; and contacting the solution with an adsorbent to remove ionic species; and one or more of A method comprising:
2. The method includes filtering the solution, the filtering step filtering the solution. The liquid is equal to or less than 2 micrometers, preferably 0.2 2. The method of claim 1, further comprising the step of filtering the mixture through a filter having a pore size of 0.45 micrometers. The method according to
3. The method further comprises washing the solution with an aqueous medium, the aqueous medium being an aqueous caustic alkali solution. , preferably aqueous sodium bicarbonate, more preferably 1 to 10 weight percent bicarbonate and optionally followed by a step of adding an aqueous sodium bicarbonate solution having a concentration of sodium.
3. The method of claim 1 or 2, further comprising the step of washing the solution with water.
4. The method includes the step of crystallizing the bisphenol A dianhydride from the solution. and the step of crystallizing the bisphenol A dianhydride optionally comprises adding a poor solvent to the 4. The method of claim 1, further comprising adding the solution and cooling to an effective temperature to provide a slurry.
2. The method according to claim 1 .
5. The anti-solvent is a non-polar solvent, and preferably, the anti-solvent is heptane, hexane, pentaerythritol, hexane ... ethane, benzene, ligroin, or a combination thereof, more preferably The method of claim 4 , wherein the anti-solvent comprises heptane.
6. The method includes contacting the solution with the adsorbent, the adsorbent being a ceramic. and wherein the method further comprises: The solution containing the adsorbent is then immersed in a solution having a particle size of 16 micrometers or less, preferably 4 to 5.5 micrometers. The method according to any one of claims 1 to 5, further comprising a step of filtering through a filter having a pore size of 1000 chromium.
13. The method according to any one of claims 1 to 12.
7. The halogen-based solvent is ortho-dichlorobenzene, para-dichlorobenzene, methadi Claims 1 to 6, comprising chlorobenzene, trichlorobenzene, or a combination thereof.
2. The method according to claim 1 .
8. The divalent bond of the bisphenol A group is preferably in the 3,3', 3,4', or 4,4' positions. The method according to any one of claims 1 to 7, wherein the 3,3'-position is preferably at the 3,3'-position.
9. The bisphenol A dianhydride is an isomer mixture, and preferably, the bisphenol A dianhydride is an isomer mixture. 10 to 100 weight percent of the bisphenol A dianhydride is bisphenol A dianhydride. More preferably, said bisphenol A group has a divalent bond at the 3,3' position. 90 to 100 weight percent of the A dianhydride is the bisphenol dianhydride of the bisphenol dianhydride. The method according to any one of claims 1 to 8, wherein the divalent bond of the Nol A group is at the 3,3' positions. 。
10. The purified bisphenol A dianhydride is Sodium ion, potassium ion, calcium ion, zinc ion, each less than 25 ppm ions, aluminum ions, titanium ions, iron ions, and phosphorus ions, and Less than 50 ppm each of phosphate, sulfate, chloride, nitrate, and nitric acid Nitrate ion, Bisphenol A produced by the method of any one of claims 1 to 9, Acid dianhydride.
11. The bisphenol A dianhydride composition is Hydrolysis of bisphenol A bisimide to form the corresponding bisphenol A tetraacid salt and contacting the bisphenol A tetraacid salt with a mineral acid to form the corresponding bisphenol A tetraacid; and contacting the bisphenol A tetraacid with a halogenated solvent to form a reaction mixture. P and Heating the reaction mixture to an effective temperature to produce the corresponding bisphenol A dianhydride. from said bisphenol A tetraacid, optionally in the presence of a mineral acid; isolating the bisphenol A dianhydride from the reaction mixture; and The method comprises the step of: In the absence of The method according to any one of claims 1 to 9.
12. The poly(etherimide) contains less than 25 ppm each of sodium ion, potassium ion, Calcium ions, zinc ions, aluminum ions, titanium ions, iron ions, and Phosphorus ion, and less than 25 ppm each of phosphate ion, sulfate ion, chloride ion, and nitrate ion The method according to any one of claims 1 to 9, further comprising the steps of: The purified bisphenol A dianhydride composition produced by the polymerization of the above with an organic diamine is Poly(etherimide)s comprising repeat units derived from
13. The organic diamine is 4,4'-diaminodiphenylsulfone, 3,4'-diaminodiphenyl phenyl sulfone, 3,3'-diaminodiphenyl sulfone, meta-phenylenediamine, para-phenylenediamine, ortho-phenylenediamine, or a combination thereof The poly(etherimide) of claim 12.
14. Preferably, the article of manufacture is an optical component, more preferably a lens.
2. An article of manufacture comprising the poly(etherimide) of claim 1.
15. formula 【Chemistry 2】 Bisphenol A tetraacid, a and R b are each independently a halogen or a monovalent C 1-6 alkyl group, and p and q are each independently an integer of 0 to 4. or in which p and q are each 0] and sodium ions, potassium ions, calcium ions, and at least one of sodium, sulfate, phosphate, nitrate, nitrite, and chloride ions.
1. A method for the purification of a bisphenol A tetraacid composition, comprising: The method further comprising: washing the bisphenol A tetraacid composition with water at a temperature of 85 to 95 degrees. P and Optionally, agitating the composition during said washing; collecting the purified bisphenol A tetraacid composition, preferably by centrifugation; 、 Including, The purified bisphenol A tetraacid composition has less than 100 ppm, preferably less than 80 ppm Sodium ions, potassium ions less than ppm, more preferably 0.1 to 75 ppm , calcium ions, and each less than 900 ppm, preferably less than 450 ppm, Preferably, 0.1 to 425 ppm of sulfate ions, phosphate ions, nitrate ions, and nitric acid ions are Contains nitrate ions, method.
Citation Information
Patent Citations
Method for purifying dianhydride
JP2006176524A
Method for controlling haze in articles made from polymer compositions
JP2008514790A
Method for producing biphenol dianhydride compositions, method for purifying biphenol dianhydride, and poly(etherimide)s derived from biphenol dianhydride
JP2022518951A
Method for the purification of biphenol tetraacid compositions and biphenol tetraacid compositions
JP2022519078A
Method for producing biphenol dianhydride compositions, method for purifying biphenol dianhydride compositions, and poly(etherimides) derived from biphenol dianhydride
JP2022519809A